Articles comprising films, optical devices, coatings, and methods of making articles
By applying a film containing resin, azo-based organic particles and Ti and O-containing particles on the surface of the optical device, the problem of insufficient thermal insulation performance and light resistance in the prior art is solved, and more efficient thermal insulation and more stable appearance color.
Patent Information
- Application Number
- CN202310077958.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-17
- Filing Date
- 2019-05-17
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2039-05-17
AI Technical Summary
While improving the thermal insulation performance and appearance color of the surface film of the optical device, the prior art has problems such as deterioration caused by infrared rays reflected through the layer interface of the film and insufficient light resistance to sunlight.
A film containing resin, azo-based organic particles and Ti and O-containing particles is used to improve the thermal insulation performance and light resistance of the film by adjusting the composition and structure of the film.
While maintaining the heat insulation effect, it is achieved to suppress film discoloration caused by sunlight, thereby improving the light resistance of the film and the stability of the appearance color.
Smart Images

Figure CN116041879B_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application with application number 201910411155.7, application date May 17, 2019, and invention name “Articles including films, optical devices, coatings, and methods for making articles”. Background of the Invention Technical Field
[0003] The present invention relates to articles comprising films, optical devices, coatings and methods of making the articles. Background Art
[0004] The present invention relates to articles including films, optical devices (e.g., lens barrels of optical devices such as cameras, video cameras, or broadcasting equipment, and camera bodies, video camera bodies, surveillance cameras, or weather cameras that can be used outdoors), and coatings.
[0005] For example, a film having the function of suppressing the temperature rise of the component caused by sunlight when the optical device is used outdoors is provided on the surface of the optical device. Figure 1 As shown, a method of reflecting incident sunlight light 1 as reflected light 2 using an infrared reflective film 4 on a substrate 5 is known as a method of suppressing the temperature rise of a component caused by sunlight. By increasing the ratio of reflected light 2 to incident light 1, the generation of heat caused by transmitted light 3 can be suppressed. White titanium dioxide having high reflectivity in the visible to infrared region or a pigment having high infrared reflectivity is generally used as a material for increasing reflectivity. For the distribution of sunlight energy, visible light accounts for 47% and infrared light accounts for 50%. Therefore, high reflectivity is required in a wide range from the visible light region to the infrared region.
[0006] The above-mentioned infrared reflective film is an external film provided on the surface of the lens barrel of the optical device, so the tinge appearance observed by the user is also important. That is, a design that allows the appearance color of the lens barrel to have a desired tinge is also required. Since optical devices are often used outdoors, in addition to heat insulation performance, light resistance under harsh sunlight conditions such as the equator is also required.
[0007] Japanese Patent Publication No. 2009-139856 (Patent Document 1) discloses that by providing a colored layer on an infrared reflective layer, the temperature rise of a lens barrel caused by infrared rays can be suppressed, and the appearance color of the lens barrel can be adjusted to a desired color. In Patent Document 1, by providing not only an infrared reflective layer and a colored layer, but also a heat insulating layer with a thickness of 500 μm-2000 μm, the heat insulation performance is also improved. The colored layer in Patent Document 1 is formed by applying a coating containing an infrared-transmitting coloring substance to the surface of the infrared reflective layer, so the appearance color of the lens barrel can be adjusted to a desired color. As described above, Patent Document 1 discloses a multilayer film that is provided on the surface of a lens barrel and satisfies both design and heat insulation performance.
[0008] Japanese Patent Publication No. 2011-085235 (Patent Document 2) discloses a heat-insulating paint for a gas cylinder, which provides a relatively high brightness (L * ) and a single-layer film with a high solar reflectivity of 40% or more. The heat-insulating paint in Patent Document 2 is described as providing good heat-insulating performance because the paint exhibits a relatively high brightness of 50 or more and 80 or less, thereby achieving a relatively high visible light reflectivity.
[0009] However, in Patent Document 1, a multilayer structure including a coloring layer, an infrared reflecting layer, and a heat insulating layer is required to achieve both design and heat insulating properties. In a multilayer film, infrared rays enter the film through undesirable interface reflections on each layer, which deteriorates the effect of reducing temperature rise and causes the film to separate and break at the interface of the layer in a harsh environment.
[0010] Patent Document 2, which provides a single-layer film, describes that inorganic heat-insulating particles, organic heat-insulating particles, or both inorganic heat-insulating particles and organic heat-insulating particles can be used to relatively increase brightness. However, organic heat-insulating particles have relatively low light resistance to sunlight, which may cause fading. SUMMARY OF THE INVENTION
[0011] An article according to one aspect of the present invention includes a resin, azo-based organic particles, and particles containing Ti and O.
[0012] An optical device according to one aspect of the present invention is an optical device including a film comprising a resin, azo-based organic particles, and particles containing Ti and O, and formed on an outer surface of the optical device.
[0013] A coating material according to one aspect of the present invention includes a resin, azo organic particles, and particles containing Ti and O. When the content of the azo organic particles is assumed to be 100 wt %, the content of the particles containing Ti and O is 10 wt % or more and 1600 wt % or less.
[0014] According to one aspect of the present invention, a method for manufacturing an article includes forming a region containing a resin and particles with an average particle size of 100 nm to 400 nm, wherein the particles contain at least one of titanium dioxide, aluminum oxide, zirconium oxide, or zinc oxide; forming a region not containing the particles with an average particle size of 100 nm to 400 nm on a portion of the surface of the region; and forming a region containing a resin and particles with an average particle size of 100 nm to 400 nm and containing at least one of titanium dioxide, aluminum oxide, zirconium oxide, or zinc oxide on the region not containing the particles.
[0015] A method of manufacturing an article according to another aspect of the present invention includes applying a coating material including a resin, an organic pigment, an inorganic pigment, and an alkanolammonium salt onto a substrate and curing the applied coating material to form a film.
[0016] Further features of the present invention will become apparent from the following description of exemplary embodiments with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a schematic cross-sectional view showing reflection and absorption of sunlight when a film to be provided on the surface of an optical device is provided on the upper surface of a substrate.
[0018] Figures 2A to 2D is a schematic cross-sectional view for describing a film according to a first embodiment.
[0019] Figure 3A and 3B is a schematic cross-sectional view for describing a film according to a first embodiment.
[0020] Figure 4A and 4B An example of an interchangeable lens for a camera including a lens barrel is shown as an optical apparatus according to one embodiment of the present invention.
[0021] Figure 5 Measuring reflectance with a spectrophotometer is schematically shown.
[0022] Figure 6 A method for evaluating the temperature is schematically shown.
[0023] Figures 7A to 7D is a schematic cross-sectional view showing a film according to a second embodiment.
[0024] Figure 8 is a schematic cross-sectional view showing a film according to a third embodiment. DETAILED DESCRIPTION
[0025] Hereinafter, embodiments of the present invention will be described.
[0026] First embodiment
[0027] First, an article including a film which is not easily subjected to discoloration (fading) caused by sunlight even if the film has a light color (high brightness) and has good heat-insulating properties will be described. Discoloration in the present invention includes discoloration caused by fading.
[0028] Method for achieving heat-insulating effect of film having high brightness and good heat-insulating performance and suppressing discoloration caused by sunlight Relationship between discoloration of azo-based organic particles caused by sunlight and heat-insulating performance
[0029] The relationship between the discoloration of the azo-based organic particles caused by sunlight and the heat shielding performance will be described.
[0030] Azo organic particles are colored pigments with a chemical structure of an azo group RN=N-R' in the molecule. Such azo organic particles have higher infrared reflection performance than inorganic pigments. When azo organic particles are irradiated with sunlight, the azo group sometimes breaks down into 2R and N 2 . The azo-based organic particles show color through the N=N contained therein and the surrounding atomic arrangement. Therefore, if N=N is cleaved, the color disappears, which increases the brightness. In this specification, azo-based organic particles are defined as colored pigments having a chemical structure of an azo group RN=N-R' in the molecule. Colored pigments whose color changes due to the cleavage of N=N of colored pigments having a chemical structure of an azo group RN=N-R' in the molecule are also considered to be azo-based organic particles.
[0031] In order to increase the reflectivity of visible light and improve the heat insulation performance, it is necessary to set the brightness on the surface of the optical device to 50 or more, and it is necessary to use azo-based organic particles with high reflectivity. If a film is formed on the surface of the optical device, it is also necessary for the film to have high brightness. It is necessary to use azo-based organic particles with high reflectivity, but it is necessary to reduce the amount of colorant to provide a film with high brightness. That is, Figure 2A As shown in FIG. 1 , the amount of azo organic particles 7 used as a colorant is reduced to the extent that the azo organic particles 7 are sparsely present in the resin 8. The extent to which the azo organic particles 7 are sparsely present means, for example, that the content of the azo organic particles is 0.1 volume % or more and 0.4 volume % or less relative to the volume of the film. When the azo group is cleaved by irradiation with sunlight 6, decolorized azo organic particles 9 are obtained. Figure 2B As shown, since the azo organic particles 7 are sparsely present in the resin 8, the ratio of the azo organic particles 9 whose azo groups have been cleaved to the azo organic particles 7 whose azo groups have not been cleaved is large. This significantly changes the color of the film formed on the surface of the optical device.
[0032] On the other hand, in a film having a relatively low brightness of less than 50, such as Figure 2C As shown in FIG. 1 , a large number of azo organic particles 7 are present in the resin 8. Therefore, even if the azo group is cleaved by irradiation with sunlight 6, the ratio of the azo organic particles 9 whose azo group has been cleaved to the azo organic particles 7 whose azo group has not been cleaved is small, as shown in FIG. Figure 2D As shown. Therefore, the color change of the film formed on the surface of the optical device is relatively small. However, the film with a brightness of less than 50 has high visible light absorption performance and low sunlight reflection performance, which deteriorates the heat insulation performance.
[0033] Method for achieving heat insulation effect and suppressing discoloration according to an embodiment of the present invention
[0034] As described above, a film having a brightness of 50 or more and including the azo-based organic particles 7 produces a large heat shielding effect, but has a disadvantage of discoloration due to sunlight.
[0035] As a result of intensive research on methods for achieving a heat-insulating effect and suppressing discoloration, the present inventors have found that discoloration caused by sunlight can be suppressed by further adding particles containing Ti and O to the film. Although described in detail later, the particles containing Ti and O may contain at least one inorganic metal in addition to Ti and O.
[0036] like Figure 3A As shown in FIG. 1 , the film according to the embodiment of the present invention comprises azo-based organic particles 7, resin 8, and particles 10 containing Ti and O. In addition, the brightness can be adjusted to 50 or more because the heat insulation effect is improved. When the film according to the embodiment of the present invention is irradiated with sunlight 6, as shown in FIG. Figure 3B As shown, the azo groups of the azo organic particles 7 are cleaved and discolored azo organic particles 9 are formed, which increases the brightness. At this time, the TiO in the Ti and O containing particles 10 is degraded due to sunlight. 2 The particles 11 containing Ti and O are excited by the photocatalytic action and form excited particles 11 containing Ti and O. The particles 11 containing Ti and O excited by the sunlight convert electrons (e - ) is released into the resin 8, and the molecular chains of the resin 8 are cleaved by the electron energy. As a result, the resin 8 becomes a discolored resin 12, and thus the brightness decreases.
[0037] In the film according to the embodiment of the present invention, the brightness of the azo-based organic particles 7 increases due to irradiation with the sunlight 6, while the brightness of the particles 10 containing Ti and O decreases. In general, discoloration is suppressed by the offset effect.
[0038] Articles according to embodiments of the present invention
[0039] The article according to the embodiment of the present invention has a surface on which a film (film according to the embodiment of the present invention) with good heat insulation performance is formed by applying the coating according to the embodiment of the present invention to a plastic or metal substrate. That is, the article according to the embodiment of the present invention includes a film (film according to the embodiment of the present invention) with good heat insulation performance on its surface. The article according to the embodiment of the present invention is particularly suitable for optical equipment. The optical equipment is, for example, an interchangeable lens for a camera, a camcorder, a broadcasting device, etc. The optical equipment is also, for example, a camera body, a camera body, a surveillance camera, or a weather camera (an image forming device that can be used outdoors and in which the image is formed by the light passing through). The optical equipment according to the embodiment of the present invention produces a greater heat insulation effect by forming a film according to the embodiment of the present invention in a portion to be irradiated by sunlight (referred to as an outer surface) when used outdoors. Figure 4A 1 is an external view of an interchangeable lens for a camera, which includes a lens barrel having a holding unit for holding the lens, and the interchangeable lens is an optical device according to an embodiment of the present invention. The interchangeable lens includes a lens barrel 30 and a tripod socket 33. The lens barrel 30 is composed of, for example, a lens, a fixed lens barrel 31 and an annular component 32. In the optical device according to an embodiment of the present invention, a film with good heat insulation performance (a film according to an embodiment of the present invention) is formed on the surface of the fixed lens barrel 31 and the annular component 32 of the lens barrel 30 and is formed on the surface of the tripod socket 33. The materials of the fixed lens barrel 31, the annular component 32 and the tripod socket 33 are not particularly limited and can be plastic or metal.
[0040] Figure 4B : is a sectional view showing a single-lens reflex digital camera connected with an interchangeable lens including a lens barrel having a holding unit for holding the lens, which is an optical apparatus according to one embodiment of the present invention.
[0041] The optical device according to an embodiment of the present invention is a device in which a film according to an embodiment of the present invention is formed, such as binoculars, a microscope, a semiconductor exposure device, an interchangeable lens, or an electronic device such as a camera. In particular, the optical device is a device equipped with an optical system including an optical element or a device that generates an image using light that has passed through the optical element.
[0042] The optical device according to an embodiment of the present invention can be a camera system, such as a digital still camera or a digital video camera, or an electronic device such as a mobile phone including an image pickup element, which receives light that has passed through the optical element of an embodiment of the present invention. A module such as a camera module installed on the electronic device can be used as an image pickup device.
[0043] exist Figure 4B , a camera body 602 and an interchangeable lens 601 serving as an optical device and including an outer barrel 620 of a lens barrel on which a film according to an embodiment of the present invention is formed are connected to each other. The interchangeable lens 601 is detachably mounted on the camera body 602.
[0044] Light from an object passes through an optical system composed of a plurality of lenses 603 and 605 arranged on the optical axis of the imaging optical system in the interchangeable lens 601, and is received by the image pickup element.
[0045] Here, the lens 605 is supported by the inner barrel 604 of the barrel, and is movably supported by the outer barrel 620 of the lens barrel for focusing and zooming.
[0046] For the observation duration before capture, light from the object is reflected by the main mirror 607 in the housing 621 of the camera body and passes through the prism 611. Then, the photographer sees the captured image through the viewfinder lens 612. The main mirror 607 is, for example, a half mirror. The light that has passed through the main mirror is reflected by the sub-mirror 608 toward the autofocus (AF) unit 613, and the reflected light is used, for example, for focusing. The main mirror 607 is mounted on and supported by the main mirror bracket 640 by bonding. During capture, the main mirror 607 and the sub-mirror 608 are moved to a position outside the optical path using a drive mechanism (not shown), the shutter 609 is opened, and the captured image incident from the lens barrel 601 is focused on the image pickup element 610. The aperture 606 is provided so that the brightness and the depth of focus during capture can be changed by adjusting the opening area.
[0047] Coating according to an embodiment of the present invention
[0048] First, a coating material and a method of preparing the coating material according to an embodiment of the present invention will be described.
[0049] The coating material according to an embodiment of the present invention includes at least a resin, azo-based organic particles, and Ti- and O-containing particles.
[0050] Azo organic particles
[0051] The azo-based organic particles contained in the coating material according to an embodiment of the present invention will be described.
[0052] The azo organic particles contained in the coating according to the embodiment of the present invention may be any particles as long as the azo organic particles are particles of a compound having an azo group. Examples of the color of the azo organic particles contained in the coating according to the embodiment of the present invention include black color, yellow color, red color and orange color. Black color can be used because the color tone (a * and b* ) changes little. The solar reflectance can be set high, and a material whose solar reflectance is greater than 10% achieved only by azo organic particles can be selected. Examples of azo organic particles include particles of nickel azo pigments, insoluble azo pigments, soluble azo pigments, high molecular weight azo pigments, and azomethine azo pigments. These azo organic particles can be used alone or in combination of two or more.
[0053] The average particle size of the azo organic particles contained in the coating according to the embodiment of the present invention is preferably 10 nm or more and 5 μm or less, and more preferably 50 nm or more and 2 μm or less. If the average particle size of the azo organic particles contained in the coating according to the embodiment of the present invention is less than 10 nm, the surface area of the particles increases. Therefore, the light resistance is deteriorated, which may cause discoloration. If the average particle size of the azo organic particles contained in the coating according to the embodiment of the present invention is greater than 5 μm, the irregularity of the coating film increases and the thickness accuracy is deteriorated, which may deteriorate the focusing accuracy, etc.
[0054] The azo particles may each have any shape. Examples of the shape include spherical, plate-like, cubic, elliptical, lamellar, hollow, star-like, needle-like, and irregular shapes. These organic azo particles may be used alone or in combination of two or more.
[0055] The content of azo organic particles in the coating according to the embodiment of the present invention relative to the non-volatile components in the coating is preferably 0.1wt% or more and 1.0wt% or less, and more preferably 0.15wt% or more and 0.5wt% or less. If the content of azo organic particles is less than 0.1wt%, the brightness of the film is excessively increased, which may deteriorate the antifouling performance. If the content of azo organic particles is 1.0wt% or more, the brightness of the film is excessively reduced, which deteriorates the solar reflectance. The content of azo particles relative to the non-volatile components in the coating can be determined by the same method as the content of azo organic particles contained in the film according to the embodiment of the present invention after the coating is cured. The method will be described later.
[0056] Particles containing Ti and O
[0057] Next, the particles containing Ti and O contained in the coating according to the embodiment of the present invention will be described. As described above, the particles containing Ti and O contained in the coating according to the embodiment of the present invention may also contain at least one inorganic metal in addition to Ti and O. When at least one inorganic metal is contained in addition to Ti and O, the color of the particles changes, so such inorganic metals can be used as particles (pigments) that change color. An example of particles containing Ti and O according to an embodiment of the present invention is titanium dioxide. Specific examples of particles containing Ti and O include (Ti, Ni, Sb) Ox, (Ti, Cr, Sb) Ox, (Ti, Fe, Zn) Ox, (Co, Cr, Zn, Al, Ti) Ox, (Co, Cr, Zn, Ti) Ox, and (Co, Al, Ni, Ti) Ox. For example, (Ti, Ni, Sb) Ox is a pigment having a crystal structure obtained by sintering titanium oxide, nickel oxide, and antimony oxide. The particles containing Ti and O according to the embodiment of the present invention are selected from titanium dioxide, (Ti, Sb, Cr) O 2 and (Ti,Fe,Zn)O 2 Particles of one material or a mixture of the above materials.
[0058] These Ti and O-containing particles are hardly coated or not coated with silica or the like having light resistance because the molecular chains of the resin need to be cracked by photocatalysis. The content of the Ti and O-containing particles relative to the non-volatile components in the coating can be measured by the same method as the content of the Ti and O-containing particles in the film according to the embodiment of the present invention after the coating is cured. This method will be described later.
[0059] The content of the particles containing Ti and O in the coating according to the embodiment of the present invention relative to the non-volatile components in the coating is preferably 0.1wt% or more and 1.6wt% or less, and more preferably 0.3wt% or more and 0.7wt% or less. If the content of the particles containing Ti and O in the coating according to the embodiment of the present invention is less than 0.1%, the photocatalytic effect during irradiation with sunlight is low, which may significantly change the brightness of the film according to the embodiment of the present invention. If the content of the particles containing Ti and O in the coating according to the embodiment of the present invention is greater than 1.6wt%, the photocatalytic effect during irradiation with sunlight is too high, which may significantly change the brightness of the film according to the embodiment of the present invention.
[0060] The average particle size of the particles containing Ti and O contained in the coating according to the embodiment of the present invention is preferably 10 nm or more and 5 μm or less, and more preferably 50 nm or more and 2 μm or less. If the average particle size of the particles containing Ti and O according to the embodiment of the present invention is less than 10 nm, the surface area of the particles increases. Therefore, the photocatalytic effect increases, which may cause discoloration. If the average particle size of the particles containing Ti and O according to the embodiment of the present invention is greater than 5 μm, the irregularity of the coating film increases and the thickness accuracy deteriorates, which may deteriorate the focusing accuracy, etc.
[0061] When the content of the azo-based organic particles in the coating material is assumed to be 100 wt %, the content of the particles containing Ti and O may be set to 10 wt % or more and 1600 wt % or less. Outside this range, the brightness may vary significantly.
[0062] Resin
[0063] Next, the resin contained in the coating material according to the embodiment of the present invention will be described.
[0064] Examples of the resin contained in the coating according to the embodiment of the present invention include epoxy resins, polyurethane resins, acrylic resins, polyurethane-acrylic resins, phenolic resins, and alkyd resins. These resins may be used alone or in combination of two or more.
[0065] The content of the resin in the coating according to the embodiment of the present invention relative to the non-volatile components in the coating is preferably 5wt% or more and 80wt% or less, and more preferably 15wt% or more and 50wt% or less. If the content of the resin according to the embodiment of the present invention is less than 5wt%, the adhesion to the substrate may be deteriorated. If the content of the resin according to the embodiment of the present invention is greater than 50wt%, the solar reflectance may be deteriorated. The content of the resin relative to the non-volatile components in the coating can be determined by the same method as the content of the resin in the film according to the embodiment of the present invention after the coating is cured. This method will be described later.
[0066] Particles for adjusting brightness (inorganic pigments)
[0067] The coating according to an embodiment of the present invention may contain particles of inorganic pigments other than particles containing Ti and O as particles for adjusting brightness. The brightness of the film according to an embodiment of the present invention is preferably 50 or more, more preferably 71 or more and 80 or less. In this specification, inorganic pigments other than particles containing Ti and O are simply referred to as inorganic pigments.
[0068] The particles (inorganic pigments) included in the coating according to the embodiment of the present invention and used to adjust the brightness to more than 50 can be any particles as long as the brightness can be adjusted. The particles (inorganic pigments) according to the embodiment of the present invention used to adjust the brightness to more than 50 preferably have a high solar reflectance, and more preferably have a solar reflectance greater than 10% achieved by the material itself. Examples of particles (inorganic pigments) according to the embodiment of the present invention used to adjust the brightness to more than 50 include titanium dioxide (titanium oxide) whose surface is coated with silicon dioxide, aluminum oxide, zirconium oxide, silicon dioxide, hollow silicon dioxide and zinc oxide. These materials can be used alone or in combination. If the brightness of the film formed using the coating according to the embodiment of the present invention is less than 50, the solar reflectance is reduced, which reduces the cooling effect. If the brightness of the film formed using the coating according to the embodiment of the present invention is greater than 80, the film is excessively whitened, which may cause obvious dirt. In this specification, titanium dioxide whose surface is coated with silicon dioxide means that at least a portion of the surface of the titanium dioxide particles is coated with silicon dioxide. The particles (inorganic pigment) for adjusting the brightness to 50 or more may be titanium oxide particles whose surfaces are coated with silicon dioxide.
[0069] Rutile titanium oxide and anatase titanium oxide can be used as titanium oxide of titanium oxide particles whose surface is coated with silica. In addition, at least part of the titanium oxide is coated with silica. If the titanium oxide is not coated with silica, the titanium oxide is significantly discolored in an oxygen-free atmosphere, which reduces the reflectivity. In addition to silica, titanium oxide can be coated with a variety of materials such as zirconium oxide, aluminum oxide and organic compounds. The average particle size of the titanium oxide particles coated with silica is 0.2 μm or more. If the average particle size of the titanium oxide particles coated with silica is less than 0.2 μm, the charge of the particles is reduced. This makes it difficult to attract the silica particles described later, which may significantly cause discoloration in an oxygen-free atmosphere. If the average particle size of the titanium oxide particles coated with silica is greater than 5 μm, the irregularity of the coating film increases and the thickness accuracy deteriorates, which may deteriorate the focusing accuracy, etc. Therefore, the average particle size of the titanium oxide particles coated with silica can be set to 5 μm or less.
[0070] The content of the particles (titanium oxide particles whose surface is coated with silica) contained in the coating according to the embodiment of the present invention and used to adjust the brightness to more than 50 is preferably 5wt% or more and 80wt% or less, and more preferably 10wt% or more and 40wt% or less. If the content of the particles (titanium oxide particles whose surface is coated with silica) used to adjust the brightness to more than 50 according to the embodiment of the present invention is less than 5wt%, the tinting strength is low, which may make it difficult to adjust the brightness to more than 50. If the content of the particles (titanium oxide particles whose surface is coated with silica) used to adjust the brightness to more than 50 is greater than 80wt%, the film may become brittle. The content of the particles used to adjust the brightness to more than 50 relative to the non-volatile components in the coating can be determined by the same method as the content of the particles contained in the film according to the embodiment of the present invention and used to adjust the brightness to more than 50 after the coating is cured. This method will be described later.
[0071] In the present specification, the titanium oxide particles whose surfaces are coated with silicon dioxide may be any titanium oxide particles as long as at least a portion of the surface of the titanium oxide particles is coated with silicon dioxide. More than 80 percent of the surface of the titanium oxide particles may be coated with silicon dioxide relative to the entire surface area of the titanium oxide particles. In the present specification, the titanium oxide particles whose surfaces are coated with silicon dioxide are an example of an inorganic pigment and an example of a particle for adjusting the brightness to 50 or more.
[0072] Silica particles
[0073] In this embodiment, silica particles may be further included. The average particle size of the silica particles may be set to be greater than 10nm and less than 110nm. When the average particle size is within the range of greater than 10nm and less than 110nm, the micro defects of the silica on the surface of the titanium dioxide particles can be filled, which suppresses discoloration in an oxygen-free atmosphere. If the average particle size of the silica particles according to this embodiment is less than 10nm, the micro defects of the silica on the surface of the titanium oxide particles are not easily filled, which may make it difficult to suppress discoloration in an oxygen-free atmosphere. If the average particle size of the silica particles included in the coating according to an embodiment of the present invention is greater than 110nm, the adsorption of titanium oxide is deteriorated, which may make it difficult to suppress discoloration in an oxygen-free atmosphere.
[0074] The silica particles may have any shape. Examples of the shape of the silica particles include spherical, amorphous, star-shaped, chain-shaped, hollow, and porous. These silica particles may be used alone or in combination of two or more.
[0075] The particle size of the silica particles 128 according to this embodiment is a number average particle size. Before applying the coating, the average particle size of the silica particles 128 can be measured by a dynamic light scattering method. When the average particle size is measured after the film is formed, a sample with a thickness of 300 nm and a size of 5 μm×5 μm is cut out at 5 locations from the film according to this embodiment, and magnified 100,000 times by a transmission electron microscope (TEM). Then, the silica particles 128 are regionally analyzed at five locations by energy dispersive X-ray spectroscopy (EDS) to determine the particle size of the silica particles 128 and calculate the average value of the particle size. Finally, the average value of the particle size at the five locations is determined. The average value of the particle size at the five locations is defined as the average particle size of the silica particles contained in the film according to this embodiment. In this embodiment, for example, when silica particles 128 having a particle size of 10 nm or more and 50 nm or less aggregate to form secondary particles, such as Figure 7C As shown, when the length of the secondary particles in the long side direction is 50 nm or more and 350 nm or less, the coating performance can be improved. In particular, branched silica particles consisting of chains of spherical silica particles 128 can be selected. When applying a coating for forming a light-shielding film, branched silica particles consisting of chains of spherical silica particles 128 are suitable because the space formed by the silica particles 128 increases, so the particles 127 can easily move.
[0076] Relative to the non-volatile components in the coating, the content of the silica particles is 0.6% by mass or more and 14% by mass or less, and preferably 1% by mass or more and 10% by mass or less. If the content of the silica particles is less than 0.6% by mass, the micro defects of the silica coated with the titanium oxide particles cannot be completely filled, which may further lead to discoloration in an oxygen-free atmosphere. If the content of the silica particles according to an embodiment of the present invention is greater than 14% by mass, the haze of the coating film deteriorates, which may deteriorate the reflectivity. The content of the silica particles relative to the non-volatile components in the coating can be determined by the same method as the content of the silica particles in the film according to the embodiment of the present invention after the coating is cured. The method will be described later.
[0077] Dispersants
[0078] The dispersant included in the coating according to this embodiment can be any dispersant, as long as the dispersant can aggregate organic pigments instead of inorganic pigments. In particular, the dispersant contains an alkanolammonium salt. Initially, the dispersant is adsorbed on the surface of the pigment particles so that the pigment particles maintain a constant distance from each other, thereby preventing the aggregation between the pigment particles. However, the dispersant in this embodiment aggregates organic pigments and disperses inorganic pigments.
[0079] The dispersant according to an embodiment of the present invention may include at least one acidic group. The dispersant according to an embodiment of the present invention may have an acid value (mgKOH / g) of 30 or more and 100 or less. When the acid value (mgKOH / g) is 30 or more and 100 or less, the organic pigment may be more appropriately precipitated on the air interface side. The amount of the added dispersant may be greater than the amount of the organic pigment. If the amount of the added dispersant is less than the amount of the organic pigment, the organic pigment is partially dispersed, which reduces the amount of the organic pigment segregated on the air interface side.
[0080] The content of the dispersant in the coating according to the embodiment of the present invention relative to the non-volatile components in the coating is preferably 0.1 wt % or more and 10.0 wt % or less and more preferably 0.15 wt % or more and 7.0 wt % or less. If the content of the dispersant is less than 0.1 wt %, the heat insulation performance is deteriorated. If the content of the dispersant is 10.0 wt % or more, the refractive index of the layer is reduced, which reduces the reflection caused by the refractive index difference.
[0081] Solvents
[0082] The solvent contained in the coating material will be described.
[0083] Any solvent can be used. Examples of solvents include water, diluents, ethanol, isopropanol and n-butanol. Other examples of solvents include ethyl acetate, propyl acetate, isobutyl acetate, butyl acetate, methyl ethyl ketone, methyl isobutyl ketone, propylene glycol monomethyl ether, toluene, xylene, acetone, cellosolve, glycol ether and ether. These solvents can be used alone or in combination of two or more.
[0084] The viscosity of the coating according to the embodiment of the present invention is preferably 10 mPa·s or more and 10000 mPa·s or less, and more preferably 50 mPa·s or more and 500 mPa·s or less. If the viscosity of the coating is less than 10 mPa·s, the thickness of the applied thermal insulation film may be reduced in some places. If the viscosity of the coating is greater than 10000 mPa·s, the coating performance of the coating may deteriorate.
[0085] Other additives
[0086] The coating according to the embodiment of the present invention may contain any other additives. Examples of additives include dispersants, curing agents, curing catalysts, plasticizers, thixotropy imparting agents, leveling agents, matting agents, preservatives, ultraviolet absorbers, antioxidants, coupling agents, and inorganic fine particles and organic fine particles for adjusting color tone other than the above fine particles.
[0087] Method for preparing coating
[0088] Hereinafter, a method of preparing a coating material according to an embodiment of the present invention will be described.
[0089] The method for preparing the coating according to the embodiment of the present invention may be any method as long as the azo organic particles, the particles containing Ti and O, and the particles for adjusting the brightness to 50 or more can be dispersed in the coating. For example, a method using a bead mill, a ball mill, a jet mill, a three-roll mixer, a planetary mixer, a mixer, an ultrasonic disperser, or a homogenizer may be employed.
[0090] Articles according to embodiments of the present invention
[0091] Next, an article according to an embodiment of the present invention will be described.
[0092] By applying the coating according to the embodiment of the present invention to a plastic or metal substrate, a film with good heat insulation performance is formed on the surface of the article according to the embodiment of the present invention (the film according to the embodiment of the present invention). That is, the embodiment can provide an article, such as an optical device, including a film that is not separated or broken on its surface, and has both good design and good heat insulation performance. Therefore, the article according to the embodiment of the present invention includes a film with good heat insulation performance (the film according to the embodiment of the present invention) on its surface. The film can be formed on the outside (the side exposed to the external environment) relative to the substrate. The film according to the embodiment of the present invention can be closely adhered to the substrate, or a primer layer for improving adhesion can be provided between the substrate and the film according to the embodiment of the present invention.
[0093] Substrate
[0094] The substrate may be formed of any material, such as metal or plastic. Examples of metals include aluminum, titanium, stainless steel, magnesium alloys, and lithium-magnesium alloys. Examples of plastics include polycarbonate resins, acrylic resins, ABS resins, and fluororesins.
[0095] The substrate may have any thickness. The thickness is preferably 0.5 mm or more and 5 mm or less, more preferably 0.5 mm or more and 2 mm or less. If the thickness is less than 0.5 mm, it is difficult to maintain the shape of the lens barrel. If the thickness is greater than 5 mm, the cost of the component increases.
[0096] Primer
[0097] Primers can be used to improve the adhesion between the substrate and the film.
[0098] The primer may be formed of any material. Examples of the material include epoxy resins, polyurethane resins, acrylic resins, silicone resins, and fluororesins. The primer may contain particles according to an embodiment of the present invention, particles other than particles according to an embodiment of the present invention, colorants, dispersants, curing agents, curing catalysts, plasticizers, thixotropy-imparting agents, leveling agents, organic colorants, inorganic colorants, preservatives, ultraviolet light absorbers, antioxidants, coupling agents, and solvent residues.
[0099] The thickness of the primer is preferably 2 μm or more and 30 μm or less, and more preferably 5 μm or more and 20 μm or less. If the thickness is less than 2 μm, the adhesion of the film may sometimes decrease. If the thickness exceeds 30 μm, the positioning accuracy may be adversely affected.
[0100] The thickness of the film according to the embodiment of the present invention
[0101] The thickness of the film according to the embodiment of the present invention can be set to 10 μm or more and 70 μm or less. If the thickness is less than 10 μm, the solar reflectivity may be deteriorated. If the thickness is greater than 70 μm, the positioning accuracy of the optical device may be adversely affected.
[0102] Methods of making items
[0103] In the method of manufacturing an article according to an embodiment of the present invention, any coating method and any curing method may be employed as long as the coating according to an embodiment of the present invention can be uniformly coated on a substrate to have a thickness of 10 μm or more and 70 μm or less.
[0104] Examples of coating methods include brush coating, spray coating, dip coating, and transfer printing. The thermal insulation film may be composed of a single coating layer or multiple coating layers, or may be grained to achieve a good design.
[0105] The curing method may be a method of leaving the coating at room temperature, a method of promoting curing by any heating process, or a method of applying ultraviolet rays. In the method of curing by a heating process, for example, a heating furnace, a heater or infrared heating may be used. The curing temperature is preferably room temperature to 400° C., and more preferably room temperature to 200° C.
[0106] As described above, a film having good heat insulation performance (film according to an embodiment of the present invention) is formed on the surface of an article according to an embodiment of the present invention by applying a coating according to an embodiment of the present invention to a plastic or metal substrate. The film thus formed contains at least a resin, azo-based organic particles, and particles containing Ti and O.
[0107] Azo organic particles
[0108] The content of azo organic particles in the film according to an embodiment of the present invention is preferably 0.1 area % or more and 0.4 area % or less, and more preferably 0.15 area % or more and 0.3 area % or less. If the content of azo organic particles is less than 0.1 area %, the brightness of the film is excessively increased, which may deteriorate the antifouling performance. If the content of azo organic particles is 0.4 area % or more, the brightness of the film is excessively reduced, which deteriorates the sunlight reflectance.
[0109] The content of azo organic particles in the film according to the embodiment of the present invention is measured by the following method. First, a cross section (3 μm × 3 μm) near the surface of the film according to the embodiment of the present invention is cut out at five locations and magnified 100,000 times by a transmission electron microscope (TEM). When the particle size is large, a cross section (10 μm × 10 μm) is cut out at five locations and magnified 30,000 times by a transmission electron microscope (TEM). Then, the azo organic particles are regionally analyzed at five locations by energy dispersive X-ray spectroscopy (EDS) to calculate the content per unit area. Finally, the content of azo organic particles in the film according to the embodiment of the present invention is calculated by the average value of the content at five locations. Since the average value of the cross-sectional area at five locations is adopted in this analysis method, the theoretical volume is substantially equal to the analysis value in this method.
[0110] Particles containing Ti and O
[0111] The content of the particles containing Ti and O in the film according to an embodiment of the present invention is preferably 0.1 area % or more and 1.0 area % or less, and more preferably 0.2 area % or more and 0.7 area % or less, relative to the cross-sectional area of the film. If the content of the particles containing Ti and O according to an embodiment of the present invention is less than 0.1 area %, the photocatalytic effect during irradiation with sunlight is low, which may significantly change the brightness of the film according to an embodiment of the present invention. If the content of the particles containing Ti and O according to an embodiment of the present invention is greater than 1.0 area %, the photocatalytic effect during irradiation with sunlight is too high, which may significantly change the brightness of the film according to an embodiment of the present invention.
[0112] The content of particles containing Ti and O in the film according to an embodiment of the present invention is measured by the following method. First, a cross section (3 μm × 3 μm) near the surface of the film according to an embodiment of the present invention is cut out at five locations and magnified 100,000 times by a transmission electron microscope (TEM). When the particle size is large, a cross section (10 μm × 10 μm) is cut out at five locations and magnified 30,000 times by a transmission electron microscope (TEM). Then, the particles are regionally analyzed at five locations by energy dispersive X-ray spectroscopy (EDS) to calculate the content per unit area. Finally, the content of particles containing Ti and O in the film according to an embodiment of the present invention is calculated by the average value of the content at five locations, and this value is defined as the content of particles containing Ti and O. In this embodiment, the content calculated by this method is expressed in area %.
[0113] The particles containing Ti and O are particles in which the contact area between the particles containing Ti and O and the resin is 20% or more relative to the surface area of the particles containing Ti and O. Specifically, a cross section cut out to calculate the content is subjected to area analysis in the same manner. When the ratio of the outline length of a specific particle in contact with the resin to the entire outline length of the cross section of the specific particle is 20% or more, the specific particle is referred to as a particle containing Ti and O.
[0114] When the content of the azo organic particles according to the embodiment of the present invention is assumed to be 100 area %, the content of the particles containing Ti and O is preferably 25 area % or more and 1000 area % or less, and more preferably 50 area % or more and 500 area % or less. If the content exceeds 1000 area %, the brightness may vary significantly. If the content is less than 25 area %, the brightness may also vary significantly.
[0115] Resin
[0116] When the cross-sectional area of the film according to the embodiment of the present invention is assumed to be 100 area%, the content of the resin in the film is preferably 5 area% or more and 80 area% or less and more preferably 30 area% or more and 60 area% or less. If the content of the resin according to the embodiment of the present invention is less than 5 area%, the adhesion to the substrate may be deteriorated. If the content of the resin according to the embodiment of the present invention is greater than 60 area%, the solar reflectance may be deteriorated.
[0117] The content of the resin in the film according to the embodiment of the present invention is measured by the following method. First, a cross section (3 μm × 3 μm) near the surface of the film according to the embodiment of the present invention is cut out at five locations and magnified 100,000 times by a transmission electron microscope (TEM). When the particle size is large, a cross section (10 μm × 10 μm) is cut out at five locations and magnified 30,000 times by a transmission electron microscope (TEM). Then, the resin is regionally analyzed at five locations by energy dispersive X-ray spectroscopy (EDS) to calculate the content per unit area. Finally, the content of the resin in the film according to the embodiment of the present invention is calculated by the average value of the content at five locations, and this value is defined as the content of the resin in the film.
[0118] Particles for adjusting brightness (inorganic pigments)
[0119] When it is assumed that the unit cross-sectional area of the film according to an embodiment of the present invention is 100 area%, the content of the particles (inorganic pigments) for adjusting the brightness in the film is preferably 10 area% or more and 80 area% or less, and more preferably 20 area% or more and 60 area% or less. If the content of the particles for adjusting the brightness according to an embodiment of the present invention is less than 10 area%, the tinting strength is low, which may make it difficult to adjust the brightness to more than 50. If the content of the particles for adjusting the brightness according to an embodiment of the present invention is greater than 80 area%, the film may become brittle.
[0120] The content of the particles (inorganic pigments) for adjusting the brightness in the film according to an embodiment of the present invention is measured by the following method. First, a cross section (3 μm × 3 μm) near the surface of the film according to an embodiment of the present invention is cut out at five locations and magnified 100,000 times by a transmission electron microscope (TEM). When the particle size is large, a cross section (10 μm × 10 μm) is cut out at five locations and magnified 30,000 times by a transmission electron microscope (TEM). Then, the particles (inorganic pigments) for adjusting the brightness are regionally analyzed at five locations by energy dispersive X-ray spectroscopy (EDS) to calculate the content per unit area. Finally, the content of the particles (inorganic pigments) for adjusting the brightness in the film according to an embodiment of the present invention is calculated by the average value of the content at five locations.
[0121] In the case where the particle (inorganic pigment) for adjusting brightness is a titanium oxide particle whose surface is coated with silica, if area analysis shows that silica partially adheres (coats) the titanium oxide particle, the particle is regarded as titanium oxide whose surface is coated with silica.
[0122] Silica particles
[0123] The content of the silica particles may be set to 1 area % or more and 10 area % or less. If the content of the silica particles is less than 1 area %, minute defects of silica coating the surface of the titanium oxide particles cannot be completely filled, which may further cause discoloration in an oxygen-free atmosphere. If the content of the silica particles is greater than 10 area %, the haze of the coating film deteriorates, which may deteriorate the reflectivity.
[0124] The content of the silica particles in the film according to the embodiment of the present invention is measured by the following method. First, a cross section (3 μm × 3 μm) near the surface of the film according to the embodiment of the present invention is cut out at five locations and magnified 100,000 times by a transmission electron microscope (TEM). When the particle size is large, a cross section (10 μm × 10 μm) is cut out at five locations and magnified 30,000 times by a transmission electron microscope (TEM). Then, the silica particles are regionally analyzed at five locations by energy dispersive X-ray spectroscopy (EDS) to calculate the content per unit area. Finally, the content of the silica particles is calculated by the average value of the content at five locations.
[0125] Other additives
[0126] The film according to the embodiment of the present invention may contain any other additives. Examples of additives include dispersants, curing agents, curing catalysts, plasticizers, thixotropy imparting agents, leveling agents, matting agents, preservatives, ultraviolet absorbers, antioxidants, coupling agents, and inorganic fine particles and organic fine particles for adjusting color tone other than the above fine particles.
[0127] Next, the characteristics of an article including the thus formed film will be described.
[0128] Solar reflectance
[0129] A portion of the article according to an embodiment of the present invention (in which at least the film according to an embodiment of the present invention is formed) may have a solar reflectance of 60% or more. When the solar reflectance is less than 60%, the cooling effect is reduced.
[0130] brightness
[0131] A portion of the article according to an embodiment of the present invention (in which at least a film according to an embodiment of the present invention is formed) preferably has a brightness of 50 or more, and more preferably has a brightness of 71 or more and 80 or less. If the brightness is less than 50, the reflectivity decreases, which reduces the cooling effect. If the brightness is 80 or more, the portion becomes white, which may deteriorate the antifouling performance.
[0132] a * and b * Range
[0133] a represents the color tone of a part of the article according to an embodiment of the present invention (in which at least a film according to an embodiment of the present invention is formed) * and b * Each of can be set to be greater than -5 and less than +5. * and b * When the value of is less than -5 or more than +5, when the organic azo pigment fades by irradiation with sunlight, * and b * The color tone represented may vary significantly.
[0134] Example
[0135] Hereinafter, suitable embodiments of the present invention will be described.
[0136] Preparation of coating materials, formation of films, and evaluation of properties of articles including the films in Examples 1 to 12 were performed by the following methods.
[0137] Evaluation of product characteristics
[0138] The brightness (L * ), a * and b * To evaluate the properties of an article including the film. A film according to an embodiment of the present invention was formed on a metal plate having a size of 30 mm×30 mm and a thickness of 1 mm to prepare a sample for measurement. The metal plate was formed of stainless steel, aluminum, titanium, or a magnesium alloy. A coating according to an embodiment of the present invention was applied to a metal plate formed of a magnesium alloy using a spin coater to have a thickness of 50 μm and fired. After firing, the L on the film of the metal plate including the film according to an embodiment of the present invention was measured using a colorimeter. * 、a * and b * Then, a light fastness tester (SUNTEST XXL+, ATLAS) was used at 50±2W / m 2 The samples were subjected to a light resistance test for 200 hours at a black panel temperature of 63°C ± 3°C under an irradiance of 100 nm (300 nm to 400 nm). After the light resistance test was completed, the L * 、a * and b * .
[0139] △L * = L after light resistance test * -L before light fastness test *
[0140] If the brightness changes (△L * ) is less than 0.3, the film is a good film with very small color tone change. If the brightness change is more than 0.3 and less than 1.0, the film is a good film. If the brightness change is more than 1.0, the film is poor and has a large color tone change.
[0141] Three-level evaluation A to C
[0142] A: Brightness change (±) is less than 0.3.
[0143] B: Brightness change (±) is 0.3 or more and less than 1.0.
[0144] C: Brightness change (±) is 1.0 or more.
[0145] Evaluation of solar reflectance
[0146] Next, the evaluation of solar reflectance will be described. Figure 5 As shown, the reflectance was measured using a spectrophotometer (U-4000, Hitachi High-Technologies Corporation) and then converted into solar reflectance.
[0147] The method for measuring the reflectivity will be described. Figure 5 As shown, incident light 1 with a wavelength of 300nm to 2500nm is allowed to enter the integrating sphere 19. First, a blank formed of an alumina sintered body with a reflectivity of 100% is set on a test sample mounting portion 20, which is tilted 5° relative to the incident light 1, and a baseline measurement is performed. Subsequently, a test sample including a film according to an embodiment of the present invention formed thereon is set on the test sample mounting portion 20 instead of the blank. Light with a wavelength of 300nm to 2500nm is allowed to enter the integrating sphere 19 and detected using a detector 21 to measure the reflectivity. Then, according to JIS-K5602 (a method for determining the solar reflectivity of a coating film), the measured reflectivity is multiplied by a weighting value (weighting coefficient) and integrated to calculate the solar reflectivity.
[0148] A film according to an embodiment of the present invention is formed on a metal plate having a size of 30 mm × 30 mm and a thickness of 1 mm to prepare a sample for measurement. The metal plate is formed of stainless steel, aluminum, titanium or a magnesium alloy. A coating according to an embodiment of the present invention is applied to a metal plate formed of a magnesium alloy using a spin coater to have a thickness of 50 μm and fired. Cellotape (CT-12M, NICHIBAN Co., Ltd.) is adhered to the upper surface of the film according to an embodiment of the present invention. A light resistance tester (SUNTEST XXL+, ATLAS) is used at 50±2 W / m 2The samples were subjected to light resistance testing for 200 hours at a black panel temperature of 63°C ± 3°C under an irradiance of 100 nm (300 nm to 400 nm). After the light resistance test was completed, the Cellotape was removed from the film. After washing with acetone, the reflectivity at a wavelength of 300 nm to 2500 nm was measured using a spectrophotometer within 24 hours, and the solar reflectivity was calculated according to JIS-K5602.
[0149] When the solar reflectance is 70% or more, the film is an excellent film because the cooling effect is high. When the solar reflectance is 60% or more and less than 70%, the film is a good film because the cooling effect is relatively high. When the solar reflectance is less than 60%, the film is a poor film because the cooling effect is reduced.
[0150] Three-level evaluation A to C
[0151] A: Solar reflectance is 70% or more.
[0152] B: The solar reflectance is 60% or more and less than 70%.
[0153] C: Solar reflectance is less than 60%.
[0154] Thermal insulation effect
[0155] Figure 6 The method for evaluating the temperature is schematically shown. Figure 6 As shown, a lamp 22, a fixture 25 for temperature measurement and a test sample 23 for temperature evaluation are used to measure temperature. A film according to an embodiment of the present invention is formed on a metal plate having a size of 100mm×100mm and a thickness of 1mm to prepare a test sample 23 for temperature evaluation. The metal plate is formed of stainless steel, aluminum, titanium or a magnesium alloy. A coating according to an embodiment of the present invention is applied to the metal plate using a spin coater to have a thickness of 50μm and fired. A white corrugated cardboard box having a size of 120mm×120mm×120mm is used as a fixture 25 for temperature measurement. A window having a size of 90mm×90mm is formed in the portion where the test sample 23 for temperature evaluation is to be installed. The lamp 22 used is HILUX MT150FD6500K (IWASAKI ELECTRICCo., Ltd.).
[0156] Subsequently, the test sample 23 for temperature evaluation was mounted on the jig 25 for temperature measurement, and a thermocouple 24 was attached to the rear surface of the test sample 23 for temperature evaluation. The jig 25 for temperature measurement on which the test sample 23 for temperature evaluation was mounted was set at a distance of 100 mm from the lamp 22. Then, the lamp 22 was operated for 60 minutes, and the temperature after 60 minutes was measured.
[0157] The temperature lowering effect was determined by calculating the difference between the temperature measured for the film in each example and the temperature measured for the black blank formed on the surface of the test specimen 23 for temperature evaluation.
[0158] A black blank was prepared by applying a coating prepared by mixing 20 g of carbon black (MA100, Mitsubishi Chemical Corporation), 100 g of epoxy resin (jER 828, Mitsubishi Chemical Corporation), 70 g of an amine curing agent (ST11, Mitsubishi Chemical Corporation) and 20 g of a diluent using a planetary mixer onto the surface of the test specimen 23 and then firing the coating.
[0159] When the cooling effect is 7°C or more, the film is a film with a very high heat-insulating effect. When the cooling effect is 3°C or more and less than 7°C, the film is a film with a relatively high heat-insulating effect. When the cooling effect is less than 3°C, the film is a film with a low heat-insulating effect.
[0160] Three-level evaluation A to C
[0161] A: The cooling effect is above 7℃.
[0162] B: The cooling effect is above 3°C and below 7°C.
[0163] C: Cooling effect is less than 5℃.
[0164] Example 1
[0165] Coating preparation
[0166] In Example 1, a coating is prepared by the following method. That is, 125g of resin (48.6% by volume based on the coating film), 0.5g of azo organic particles (0.2% by volume based on the coating film) and 4.5g of particles containing Ti and O (0.7% by volume based on the coating film) are weighed. In addition, 150g of particles (inorganic pigments) for adjusting brightness (28.6% by volume based on the coating film), 5g of dispersant (3.5% by volume based on the coating film) and 100g of solvent are weighed. They are stirred for 15 hours using a ball mill to obtain a main agent. 1 gram of curing agent (18.4% by volume) is mixed with 10g of the obtained main agent to prepare the coating in Example 1.
[0167] The resin used was Olester Q-691 (Mitsui Chemicals, Inc.). The azo organic particles used were CHROMOFINE BLACK A1103 (Dainichiseika Color & Chemicals Mfg. Co., Ltd.). The particles containing Ti and O used were #5950 (Asahi sangyo Kaisha, Ltd.). The particles (inorganic pigment) used to adjust the brightness were D-970 (SAKAI CHEMICAL INDUSTRY Co., Ltd., average particle size 0.26 μm, titanium dioxide coated with silica). The curing agent used was Takenate D-120N (Mitsui Chemicals, Inc.).
[0168] Film formation
[0169] In Example 1, a film was formed by the following method: The coating material was applied to a metal plate formed of a magnesium alloy using a spin coater to have a thickness of 50 μm, dried overnight at room temperature, and then fired at 130° C. for 30 minutes to obtain the film in Example 1.
[0170] Examples 2 to 13
[0171] In Examples 2 to 13, coatings and films were prepared in the same manner as in Example 1, except that the materials and conditions listed in Tables 1 and 2 were used.
[0172] (Ti,Ni,Sb)O used 2 The particles were Yellow 5000 (Asahi sangyo Kaisha, Ltd.). The hollow silica used was Sphericel-110P8 (Potters-Ballotini Co., Ltd.). The nickel azo particles used were CI Pigment Yellow 150. The Fe-Zn particles used were Brown 4123 (Asahi sangyo Kaisha, Ltd.). The Co-Al-Ni-Ti particles used were Green 2024 (Asahi sangyo Kaisha, Ltd.). The Co-Al particles used were CoBlue 1024 (Asahi sangyo Kaisha, Ltd.).
[0173] TiO used 2 The particles were HT0110 (TOHO TITANIUM Co., Ltd.).
[0174]
[0175]
[0176] Evaluation results
[0177] Tables 3 and 4 show the brightness changes (ΔL * ), the solar reflectance (R) after the light fastness test, and the cooling effect results before and after the light fastness test.
[0178] Although containing azo organic particles, the brightness change (△L * ) is reduced to less than 1.0, ideally less than 0.3 to evaluate the results.
[0179] For the heat-insulating effect, the solar reflectance is preferably 60% or more and less than 70%, and more preferably 70% or more. The cooling effect is preferably 3°C or more and less than 7°C, and more preferably 7°C or more.
[0180] Table 3 shows the brightness change, solar reflectance and cooling effect after the light resistance test evaluated for the film in Example 1, in which acrylic polyol, azomethine black, (Ti, Sb, Cr)O 2 , titanium dioxide coated with silicon dioxide and a dispersant and the brightness was adjusted to 76. The brightness change was less than 0.3, which was an excellent result. The solar reflectance was 60% or more and less than 70%, which was a good result. The cooling effect was 3°C or more and less than 7°C, which was a good result.
[0181] Table 3 shows the brightness change before and after the light resistance test, solar reflectance, and cooling effect evaluated for the film in Example 2, wherein the content of azomethine black in Example 1 was reduced to 0.1 volume % and (Ti, Sb, Cr)O 2 The content of was reduced to 0.1 volume%. The brightness change was less than 0.3, which was an excellent result. The solar reflectance was more than 70%, which was an excellent result. The cooling effect was more than 7°C, which was an excellent result.
[0182] Table 3 shows the brightness change before and after the light resistance test, solar reflectance, and cooling effect evaluated for the film in Example 3, in which the content of azomethine black in Example 1 was increased to 0.4 volume % and (Ti, Sb, Cr)O 2 The content of was increased to 1 volume %. The brightness change was less than 0.3, which was an excellent result. The solar reflectance was 60% or more and less than 70%, which was a good result. The cooling effect was 3°C or more and less than 7°C, which was a good result.
[0183] Table 3 shows the brightness change before and after the light resistance test, solar reflectance, and cooling effect evaluated for the film in Example 4, in which (Ti, Ni—Sb)O 2 Instead of (Ti, Sb, Cr)O in Example 1 2 The change in brightness was less than 0.3, which was an excellent result. The solar reflectance was 60% or more and less than 70%, which was a good result. The cooling effect was 3°C or more and less than 7°C, which was a good result.
[0184] Table 3 shows the brightness change before and after the light resistance test, solar reflectance, and cooling effect evaluated for the film in Example 5, in which hollow silica with thermal insulation properties was used instead of the titanium oxide coated with silica in Example 1. The brightness change was less than 0.3, which is an excellent result. The solar reflectance was less than 60%, but the hollow silica had good thermal insulation properties. Therefore, the cooling effect was 3°C or more and less than 7°C, which is a good result.
[0185] Table 3 shows the brightness change before and after the light resistance test, solar reflectance, and cooling effect evaluated for the film in Example 6, in which nickel azo was used instead of azomethine black in Example 1. The brightness change was less than 0.3, which is an excellent result. The solar reflectance was 60% or more and less than 70%, which is a good result. The cooling effect was 3°C or more and less than 7°C, which is a good result.
[0186] Table 4 shows the brightness change before and after the light resistance test, solar reflectance, and cooling effect evaluated for the film in Example 7, in which Fe-Zn particles as another pigment were added to the coating in Example 1 to convert a * Adjusted to +6. Brightness change was 0.3 or more and less than 1.0, which was a good result. Solar reflectance was 60% or more and less than 70%, which was a good result. Cooling effect was 3°C or more and less than 7°C, which was a good result.
[0187] Table 4 shows the brightness change before and after the light resistance test, solar reflectance, and cooling effect evaluated for the film in Example 8, in which 0.2 volume % of (Co-Al-Ni-Ti)O 2 Added to the coating in Example 1 to convert a * Adjusted to -6. Brightness change was 0.3 or more and less than 1.0, which was a good result. Solar reflectance was 60% or more and less than 70%, which was a good result. Cooling effect was 3°C or more and less than 7°C, which was a good result.
[0188] Table 4 shows the brightness change before and after the light resistance test, solar reflectance and cooling effect evaluated for the film in Example 9, where the (Ti, Sb, Cr)O2 The content of b was increased to 1.63 volume % * Adjusted to +6. Brightness change was 0.3 or more and less than 1.0, which was a good result. Solar reflectance was 60% or more and less than 70%, which was a good result. Cooling effect was 3°C or more and less than 7°C, which was a good result.
[0189] Table 4 shows the brightness change before and after the light resistance test, solar reflectance, and cooling effect evaluated for the film in Example 10, in which Co-Al was added to the coating in Example 1 to change b * Adjusted to -6. Brightness change was 0.3 or more and less than 1.0, which was a good result. Solar reflectance was 60% or more and less than 70%, which was a good result. Cooling effect was 3°C or more and less than 7°C, which was a good result.
[0190] Table 4 shows the brightness change before and after the light resistance test, solar reflectance and cooling effect evaluated for the film in Example 11, in which titanium dioxide was added instead of (Ti, Sb, Cr)O in Example 1. 2 The brightness change was 0.3 or more and less than 1.0, which was a good result. The solar reflectance was 60% or more and less than 70%, which was a good result. The cooling effect was 3°C or more and less than 7°C, which was a good result.
[0191] Table 4 shows the brightness change before and after the light resistance test, solar reflectance, and cooling effect evaluated for the film in Example 12, in which the content of azomethine black in Example 1 was increased to 0.94 volume % and (Ti, Sb, Cr)O 2 The content of was increased to 1.61 volume % to adjust the brightness to 50. The brightness change was less than 0.3, which was an excellent result. The solar reflectance was 60% or more and less than 70%, which was a good result. The cooling effect was 3°C or more and less than 7°C, which was a good result.
[0192] Table 4 shows the brightness change before and after the light resistance test, solar reflectance, and cooling effect evaluated for the film in Example 13, in which the content of azomethine black in Example 1 was increased to 1.11 volume % and (Ti, Sb, Cr)O 2 The content of Ti and O was increased to 1.6 volume%. The brightness change was less than 0.3, which is an excellent result. However, the brightness was excessively reduced, so the solar reflectance was as low as less than 60%. The cooling effect was less than 3°C, which is a poor result. It can be clearly seen from this result that even if a large amount of azomethine black is added, the brightness change can be suppressed by adding particles containing Ti and O. However, adding a large amount of azomethine black reduces the brightness, thereby reducing the solar reflectance, thereby reducing the cooling effect. Therefore, it was found that the brightness was ideally adjusted to more than 50.
[0193] Table 3
[0194]
[0195] Table 4
[0196]
[0197] Comparative Examples 1 and 2
[0198] Preparation of coating materials for comparison, film formation, evaluation of film properties, evaluation of brightness change, evaluation of solar reflectance, and evaluation of cooling effect were performed in the same manner as in Examples 1 to 13. Only the differences from Examples 1 to 13 will be described below.
[0199] Table 5 shows the materials and contents of the films in Comparative Examples 1 and 2. Table 6 shows the evaluation results of the films in Comparative Examples 1 and 2.
[0200] Table 5 shows the brightness change before and after the light resistance test, the solar reflectance, and the cooling effect evaluated for the film in Comparative Example 1, in which Fe-Cr (Black 6350, Asahi sangyo Kaisha, Ltd.) was added instead of the azomethine black in Example 1. Since no azo-based organic particles were contained, the brightness change was as low as less than 0.3. However, the solar reflectance was less than 60%, which was a poor result. The cooling effect was less than 3°C, which was a poor result.
[0201] Table 5 shows the brightness change before and after the light resistance test, solar reflectance, and cooling effect evaluated for the film in Comparative Example 2, in which (Ti, Sb, Cr)O 2 Added to the coating in Example 1. Brightness change was 1.0 or more, which is a poor result. Solar reflectance was 60% or more and less than 70%, which is a good result. Cooling effect was 3°C or more and less than 7°C, which is a good result.
[0202] Table 5
[0203]
[0204]
[0205] Table 6
[0206] Film in Comparative Example 1 Film in Comparative Example 2 Brightness changes A C Solar reflectance C B Thermal insulation effect C B
[0207] Second embodiment
[0208] refer to Figures 7A to 7DAn article according to an embodiment of the present invention on which a film having good heat insulation performance and water resistance has been formed is described. The same description as in the first embodiment may be omitted.
[0209] Material
[0210] Figures 7A to 7D An article is shown in which a film 122 is formed on at least a portion of a surface 121 of a substrate 120 . Fig. 7A is a cross-sectional view of an article according to this embodiment. Figure 7B yes Fig. 7A Schematic enlargement of area 125 in FIG. Figure 7C Aggregated silica particles are shown. Fig.7D is a SEM image of a cross section of an object. Fig.7D An example is shown in which the substrate 120 includes a primer layer. Figures 7A to 7D , the article according to this embodiment includes a substrate 120 and a film 122. The film 122 includes at least a resin 126 and particles 127 having an average particle diameter of 100 nm or more and 400 nm or less. The film 122 according to this embodiment includes a region 124 containing particles 127 having an average particle diameter of 100 nm or more and 400 nm or less and a region 123 not containing particles 127 having an average particle diameter of 100 nm or more and 400 nm or less. In this specification, the region containing particles 127 having an average particle diameter of 100 nm or more and 400 nm or less is referred to as a particle region 124. The region not containing particles 127 having an average particle diameter of 100 nm or more and 400 nm or less is referred to as a resin region 123.
[0211] Resin
[0212] Next, the resin 126 contained in the film 122 according to this embodiment will be described.
[0213] Examples of the resin in this embodiment include epoxy resins, polyurethane resins, acrylic resins, polyurethane-acrylic resins, phenolic resins, and alkyd resins. These resins may be used alone or in combination of two or more.
[0214] The content of the resin 126 according to this embodiment is preferably 10 area % or more and 80 area % or less in the cross section of the film, and more preferably 15 area % or more and 70 area % or less. In this specification, the cross section of the film is a cross section parallel to the normal direction of the surface 121 of the substrate 120 or the surface 1220 of the film 122, and has an area of 30 μm×30 μm. The cross section is ideally a cross section parallel to the normal direction, but it may also be a cross section inclined at about 10° relative to the normal direction. If the thickness is 30 μm or less, one side of the cross section may be 30 μm or less.
[0215] If the content of the resin 126 according to the embodiment is less than 10 area %, the adhesion to the substrate 120 may be deteriorated. If the content of the resin 126 according to the embodiment is greater than 80 area %, the solar reflectance may be deteriorated. The content of the resin 126 according to the embodiment is measured by the following method. First, a sample with a thickness of 300nm and a size of 5μm×5μm is cut out from the film 122 according to the embodiment at 5 locations, and magnified 100000 times by a transmission electron microscope (TEM). Then, the resin is regionally analyzed at five locations by energy dispersive X-ray spectroscopy (EDS) to calculate the content per unit area. Finally, the content of the resin 126 in the film 122 according to the embodiment of the present invention is calculated by the average value of the content at five locations. In this embodiment, the content calculated by this method is expressed in area %.
[0216] White pigment
[0217] Next, a white pigment (which may be referred to as a first particle or simply referred to as a particle in this specification) as a particle 127 included in the film 122 according to the embodiment will be described. The film 122 according to the embodiment may have a high solar reflectance and may have a white color and a high refractive index. When the film 122 includes the particle 127, the film 122 has a white color and a high refractive index. The particle 127 is a particle of at least one of titanium dioxide, aluminum oxide, zirconium oxide, or zinc oxide. In particular, titanium dioxide particles having a high refractive index and whose surface is coated with silicon dioxide may be used because photocatalytic activity may be suppressed and thus degradation of the surrounding resin may be reduced.
[0218] The average particle size of the particles 127 can be set to be more than 100nm and less than 400nm. If the average particle size is less than 100nm, it is difficult to reflect sunlight. If the average particle size is greater than 400nm, the water resistance is deteriorated. Although described in detail later, due to the different hydrophilicity between the resin 126 and the particles 127, water is introduced into the film through the interface between the resin 126 and the particles 127. In addition, if the average particle size is greater than 400nm, the continuous contact area with the resin 126 increases, and a very large amount of water is introduced into a part of the film, which significantly reduces the water resistance. The particle size of the particles 127 according to this embodiment is determined by the following method. First, a sample with a thickness of 300nm and a size of 5μm×5μm is cut out from the film 122 according to this embodiment at 5 locations, and amplified 100000 times by a transmission electron microscope (TEM). Then, the particles 127 are regionally analyzed at five locations by energy dispersive X-ray spectroscopy (EDS) to determine the particle size of each particle and calculate the average value of the particle size. Finally, the average value of the particle diameters at the five positions is determined. The average value at the five positions is defined as the average particle diameter of the particles 127 contained in the film according to this embodiment.
[0219] The content of the particles 127 according to the embodiment is preferably 10 area % or more and 60 area % or less in the cross section of the film 122 according to the embodiment, and more preferably 15 area % or more and 50 area % or less. If the content of the particles 127 is less than 10 area %, the covering power of sunlight is reduced, and the film 122 will not act as a film with good heat insulation performance. If the content of the particles 127 according to the embodiment is greater than 90 area %, the film may become brittle. The content of the particles 127 is measured by the following method. First, a sample with a thickness of 300nm and a size of 5μm×5μm is cut out from the film according to the embodiment at 5 locations, and is magnified 100000 times by a transmission electron microscope (TEM). Then, the particles are regionally analyzed at five locations by energy dispersive X-ray spectroscopy (EDS) to calculate the content per unit area. Finally, the content of the particles 127 in the film 122 according to the embodiment of the present invention is calculated by the average value of the content at five locations. In this embodiment, the content calculated by this method is expressed in area %.
[0220] Silica particles
[0221] The film 122 according to this embodiment may contain silica particles 128. The number average particle size of the silica particles 128 is preferably 50 nm or more and 350 nm or less, and more preferably 150 nm or more and 300 nm or less. If the average particle size of the silica particles 128 is less than 50 nm, the thixotropy of the coating material used to form the film is reduced, which deteriorates the coating performance. The fine particles may have, for example, a spherical shape, a spherical shape, an ellipsoidal shape, a cuboid shape, a cubic shape, or a combination of the foregoing, or an amorphous shape.
[0222] The particle size of the silica particles 128 according to this embodiment is a number average particle size. Before applying the coating, the average particle size of the silica particles 128 can be measured by a dynamic light scattering method. When the average particle size is measured after the film is formed, a sample with a thickness of 300 nm and a size of 5 μm×5 μm is cut out from the film according to this embodiment at 5 locations, and magnified 100,000 times by a transmission electron microscope (TEM). Then, the silica particles 128 are regionally analyzed at five locations by energy dispersive X-ray spectroscopy (EDS) to determine the particle size of each silica particle 128, and the average value of the particle size is calculated. Finally, the average value of the particle size at the five locations is determined. The average value at the 5 locations is defined as the average particle size of the silica particles contained in the film according to this embodiment. In this embodiment, for example, when silica particles 128 having a particle size of 10 nm or more and 50 nm or less aggregate to form secondary particles, such as Figure 7CAs shown, when the length in the long side direction of the secondary particles is 50 nm or more and 350 nm or less, the coating performance can be improved. In particular, branched silica particles consisting of chains of spherical silica particles 128 can be selected. When applying a coating for forming a light-shielding film, branched silica particles consisting of chains of spherical silica particles 128 are suitable because the space formed by the silica particles 128 increases, so the particles 127 can easily move.
[0223] In the cross section of the film according to the embodiment, the content of the silica particles 128 is preferably 2.5 area % or more and 15.0 area % or less, and more preferably 2.5 area % or more and 10.0 area % or less. If the content of the silica particles 128 is less than 2.5 area %, the thixotropy of the coating is reduced, which deteriorates the coating performance. If the content of the silica particles 128 is greater than 15.0 area %, the thermal insulation performance is deteriorated. The content of the silica particles 128 is measured by the following method. First, a sample with a thickness of 300nm and a size of 5μm×5μm is cut out from the film according to the embodiment at 5 locations, and magnified 100000 times by a transmission electron microscope (TEM). Then, the silica particles 128 are regionally analyzed at five locations by energy dispersive X-ray spectroscopy (EDS) to calculate the content per unit area. Finally, the content of the silica particles 128 in the film according to the embodiment of the present invention is calculated by the average value of the content at five locations. In this embodiment, the content calculated by this method is expressed in units of area %.
[0224] Colorants
[0225] The film 122 according to this embodiment may optionally contain a pigment other than the white pigment used as the particles 127 as a colorant to allow the appearance to have a design. In this specification, the pigment other than the white pigment may be simply referred to as a "pigment".
[0226] The pigment according to this embodiment is preferably capable of increasing the brightness (L * ) is adjusted to 71 or more, and it is more preferable to be able to adjust the brightness to 71 or more and 85 or less. If the brightness of the thermal insulation film according to this embodiment is less than 71, the sunlight reflectance is reduced, which reduces the cooling effect. If the brightness of the thermal insulation film according to an embodiment of the present invention is greater than 85, the amount of visible light absorbed by the pigment is reduced, which may produce a glare feeling due to the reflection of visible light. The pigment according to this embodiment may reflect or transmit infrared rays.
[0227] The pigment according to this embodiment is a colorant, and may be an organic pigment, an inorganic pigment, or a combination of an organic pigment and an inorganic pigment.
[0228] The brightness in this embodiment is a value measured using a colorimeter (SE-7700, NIPPON DENSHOKU INDUSTRIES Co., Ltd.).
[0229] Examples of organic pigments include azomethine black and perylene pigments. Examples of inorganic pigments include Co-Zn-Si, Co-Al, Co-Al-Cr, Co-Al-Cr-Zn, Co-Al-Zn-Ti, Co-Ni-Zn-Ti, Ti-Cr-Sb, Ti-Fe-Zn, Fe-Zn and Fe-Cr. Other examples of inorganic pigments include Mn-Bi, Co-Cr-Zn-Sb, Cu-Cr, Cu-Cr-Mn, Cu-Fe-Mn, Mn-Y, Mn-Sr, Co-Cr-Zn-Al-Ti, Co-Cr-Zn-Ti, Ti-Cr-Sb and P-Ba-Sr.
[0230] Organic Pigments
[0231] The azo organic particles may be any particles as long as they are particles of a compound having an azo group. Examples of the color of the azo organic particles according to this embodiment include black colors, yellow colors, red colors, and orange colors. Black colors may be used because the color tone (a * and b * ) changes little. The solar reflectance can be set high, and a material whose solar reflectance is greater than 10% achieved only by azo-based organic particles can be selected. Examples of azo-based organic particles include particles of nickel azo pigments, insoluble azo pigments, soluble azo pigments, high molecular weight azo pigments, and azomethine azo pigments. These organic azo particles can be used alone or in combination of two or more.
[0232] The average particle size of the organic pigment according to this embodiment is preferably 0.1 μm or more and 5.0 μm or less, and more preferably 0.1 μm or more and 2.0 μm or less. If the average particle size of the organic pigment according to this embodiment is less than 0.1 μm, the surface area of the particles increases. Therefore, the light resistance deteriorates, which may cause discoloration. If the average particle size of the organic pigment according to this embodiment is greater than 5.0 μm, the irregularity of the coating film increases and the thickness accuracy deteriorates. Therefore, when this embodiment is applied to a lens barrel, the focusing accuracy, etc. may deteriorate.
[0233] The average particle size in this embodiment is the average value of the particle sizes of a plurality of resin particles. The average particle size of the resin particles is determined by dispersing the particles in water and analyzing them by laser scattering. In this embodiment, the average particle size of the resin particles is the volume average particle size.
[0234] The organic pigment may be particles having any shape. Examples of the shape include sphere, cube, ellipse, plate, layer, chain, hollow, star, needle, and special shape. In particular, for example, plate, layer, and chain that easily cause segregation on the air interface side due to aggregation of the organic pigment may be used.
[0235] These organic pigments may be used alone or in combination of two or more as long as the design and heat insulation performance are not impaired.
[0236] When the total amount of the coating is assumed to be 100 wt%, the content of the organic pigment in the coating according to this embodiment is preferably 0.01 wt% or more and 1.0 wt% or less, and more preferably 0.015 wt% or more and 0.5 wt% or less. If the content of the organic pigment is less than 0.01 wt%, the brightness of the film is excessively increased, which may deteriorate the design and may also deteriorate the antifouling performance. If the content of the organic pigment is 1.0 wt% or more, the brightness of the film is excessively reduced, which deteriorates the heat insulation performance.
[0237] Inorganic Pigments
[0238] The inorganic pigment used in this embodiment can be any inorganic pigment, as long as the inorganic pigment has good heat insulation performance, and can contain the titanium dioxide particles whose surface is coated with silicon dioxide.Especially, the inorganic pigment also contains the colored inorganic pigment for adjusting the color.The inorganic pigment can contain the particles containing Ti and O that are not coated on its surface.The particles containing Ti and O that are not coated on its surface can be colored inorganic pigment.In this embodiment, the particles containing Ti and O that are not coated on its surface can be referred to as particles containing Ti and O.
[0239] Since titanium dioxide itself has a high refractive index, the refractive index of the film can be easily adjusted to a desired refractive index. Due to the bright color of titanium dioxide itself, the color tone of the coating film can also be easily adjusted to a desired color tone. In addition, a large amount of titanium dioxide products containing sufficiently fine particles can be commercially obtained at a relatively low cost, so titanium dioxide can be appropriately used.
[0240] The content of the titanium dioxide particles whose surfaces are coated with silicon dioxide in the film according to this embodiment is preferably 10wt% or more and 70wt% or less, and more preferably 20wt% or more and 60wt% or less relative to the resin composition. If the content is less than 10wt%, the infrared reflection effect may not be sufficiently produced. If the content is greater than 70wt%, sufficient film quality may not be obtained. When particles whose surfaces are coated with silicon dioxide are used, photocatalytic activity may be suppressed, which may suppress the degradation of surrounding resins.
[0241] The average particle size of the titanium dioxide particles whose surfaces are coated with silica according to this embodiment is preferably 0.1 μm or more and 1.5 μm or less, more preferably 0.1 μm or more and 1.0 μm or less. If the average particle size is less than 0.1 μm, the surface area of the particles increases, and the titanium dioxide particles whose surfaces are coated with silica are prone to aggregation, which makes it difficult to properly disperse the titanium dioxide particles in the film. Although described in detail later, if the average particle size is greater than 1.5 μm, the segregation of the organic pigment to the air interface side is suppressed, and the design and thermal insulation performance cannot be fully achieved. The titanium dioxide particles whose surfaces are coated with silica according to this embodiment are defined as particles in which at least a portion of the surface is coated with silica. The average particle size of the titanium dioxide particles whose surfaces are coated with silica according to this embodiment represents the equivalent spherical diameter of the particles that are not aggregated.
[0242] Titanium dioxide particles coated with silicon dioxide on their surfaces according to this embodiment can be prepared by a known method such as a gas phase method or a liquid phase method, as long as the required refractive index and the required average particle size are met. Examples of the method include a method in which a metal powder is charged into a flame and burned in an atmosphere containing at least oxygen to synthesize titanium dioxide fine particles and a sol-gel method in which titanium alkoxide is hydrolyzed and polycondensed in the presence of a catalyst. Titanium dioxide is known to have a crystalline structure, such as a rutile structure or anatase structure, which exhibits a higher refractive index than an amorphous structure. However, as long as the required particle size is met, titanium dioxide having any crystalline form can be suitably used.
[0243] In addition to the titanium dioxide particles whose surface is coated with silicon dioxide, the inorganic pigment according to this embodiment may contain colored inorganic pigments. The content of the infrared reflective colored inorganic pigment according to this embodiment is preferably 0.01% by weight or more and 2.0% by weight or less, more preferably 0.02% by weight or more and 1.5% by weight or less. If the content of the infrared reflective colored inorganic pigment according to this embodiment is less than 0.01wt%, the photocatalytic effect during irradiation with sunlight is low, which may significantly change the appearance tone of the film according to this embodiment. If the content of the infrared reflective colored inorganic pigment according to this embodiment is greater than 2.0wt%, the thermal insulation performance may deteriorate. The infrared reflective colored inorganic pigment according to this embodiment can be uniformly dispersed in the film.
[0244] The inorganic pigment according to this embodiment may further contain particles containing Ti and O whose surfaces are not coated. The particles containing Ti and O are hardly coated with or not coated with silica or the like having light resistance, because the molecular chains of the resin need to be cracked by photocatalysis. This is because irradiation with sunlight reduces the brightness of the film by using the photocatalytic effect of the particles containing Ti and O whose surfaces are not coated. The reasons are as follows. The azo-based organic particles used as organic pigments are colored pigments having a chemical structure of an azo group RN=N-R' in the molecule. The azo-based organic particles have a higher infrared reflectivity than inorganic pigments. However, when the azo-based organic particles are irradiated with sunlight, the azo group is cracked into 2R and N 2 . Azo-based organic particles show color by the N=N contained therein and the surrounding atomic arrangement. Therefore, if N=N is cleaved, the color disappears, which increases the brightness. That is, the color of the film formed on the surface of an item such as an optical device can change significantly. This change appears significantly when the content of the azo-based organic particles decreases.
[0245] Due to sunlight, TiO in the Ti and O-containing particles 10 2 The Ti and O-containing particles excited by sunlight transfer electrons (e - ) is released into the resin, and the molecular chains of the resin are cleaved by the electron energy. As a result, the resin becomes a discolored resin, so the brightness decreases.
[0246] In the film according to the embodiment of the present invention, the brightness of the azo organic particles increases due to irradiation with sunlight, while the brightness of the particles containing Ti and O decreases. In general, the offset effect suppresses discoloration. The particles containing Ti and O include particles containing only Ti and O (e.g., titanium dioxide particles) and / or particles containing at least one inorganic metal in addition to Ti and O. Examples of particles containing at least one inorganic metal in addition to Ti and O according to this embodiment include (Ti, Ni, Sb) Ox, (Ti, Cr, Sb) Ox, (Ti, Fe, Zn) Ox, (Co, Cr, Zn, Al, Ti) Ox, (Co, Cr, Zn, Ti) Ox, and (Co, Al, Ni, Ti) Ox. Examples of particles containing Ti and O according to an embodiment of the present invention include (Ti, Ni, Sb) Ox, (Ti, Cr, Sb) Ox, (Ti, Fe, Zn) Ox, (Co, Cr, Zn, Al, Ti) Ox, (Co, Cr, Zn, Ti) Ox, and (Co, Al, Ni, Ti) Ox. When particles containing Ti and O are contained, the content may be set to 1.6 wt% or less.
[0247] The pigment according to this embodiment can be a pigment of any color. Examples of colors include black, brown, yellow, red, blue, purple, pink, green and orange. These pigments can be used alone or in combination of two or more.
[0248] The content of the pigment according to the embodiment in the cross section of the film according to the embodiment can be set to 15 area % or less. If the content of the pigment according to the embodiment of the present invention is greater than 15 area %, the hue of the coating film deepens, which may reduce the brightness. The content of the pigment is measured by the following method. First, a sample with a thickness of 300nm and a size of 5μm×5μm is cut out from the film according to the embodiment at 5 locations, and magnified 100000 times by a transmission electron microscope (TEM). Then, the pigment is regionally analyzed at five locations by energy dispersive X-ray spectroscopy (EDS) to calculate the content per unit area. Finally, the content of the pigment in the film according to the embodiment of the present invention is calculated by the average value of the content at five locations. In this embodiment, the content calculated by this method is expressed in area %.
[0249] Other additives
[0250] The film for optical devices according to the embodiment of the present invention may contain any other additives. Examples of additives include dispersants, curing agents, curing catalysts, plasticizers, thixotropy imparting agents, leveling agents, matting agents, preservatives, ultraviolet absorbers, antioxidants, coupling agents, and inorganic fine particles and organic fine particles for adjusting color tone other than the above fine particles.
[0251] Next, a method for improving water resistance while maintaining the heat insulation effect of the heat insulation film will be described.
[0252] Method for improving water resistance while maintaining the thermal insulation effect of thermal insulation film
[0253] Water resistance of thermal insulation film
[0254] The film 122 containing the resin 126 and the particles 127 having an average particle size of 100 nm or more and 400 nm or less absorbs water from the film surface in rainy weather or a high humidity atmosphere. This is because: due to the difference in hydrophilicity between the resin 126 and the particles 127 having an average particle size of 100 nm or more and 400 nm or less, water is introduced into the film through the interface between the resin 126 and the particles 127. Water is increasingly introduced into the film through the interface between the resin 126 and the particles 127, and is also unevenly distributed to the interface 129 between the film 122 and the substrate 120. If the film 122 and the substrate 120 expand or contract due to temperature changes in the presence of water, the difference in expansion coefficient between the film 122 and the substrate 120 causes defects such as film floating and separation at the interface 129 between the film 122 and the substrate 120 and swelling caused by the reaction between the substrate 120 and water. In order to obtain good thermal insulation performance, it is desirable that the content of particles 127 having an average particle size of 100 nm or more and 400 nm or less in the film is increased as much as possible. However, this increases the number of paths for water in the film, which increases the amount of water at the interface 129 between the film 122 and the substrate 120. Method for improving water resistance while maintaining the thermal insulation effect of a thermal insulation film according to an embodiment of the present invention
[0255] As described above, it has been found that improvements in both thermal insulation performance and water resistance cannot be achieved in the prior art.
[0256] As a result of intensive research on a method of maintaining heat insulation performance and improving water resistance, the present inventors have found that a resin region 123 that does not contain particles 127 having an average particle diameter of 100 nm or more and 400 nm or less and separates the interface between the resin 126 and the particles 127 is provided in the film 122. Specifically, the resin region 123 that does not contain particles 127 having an average particle diameter of 100 nm or more and 400 nm or less is provided in a region (particle region 124) containing the particles 127. Therefore, water resistance can be improved while maintaining heat insulation performance.
[0257] Resin area
[0258] The region 123 (resin region) not including the particles 127 having an average particle diameter of 100 nm or more and 400 nm or less according to this embodiment will be described.
[0259] Figures 7A to 7D The resin region 123 shown is a region containing at least a resin 126 and optionally the above-mentioned additives. Examples of the resin 126 include epoxy resins, polyurethane resins, acrylic resins, polyurethane-acrylic resins, phenolic resins, and alkyd resins.
[0260] The refractive index in the resin region may be set lower than that in the particle region. When the refractive index in the resin region is lower than that in the particle region, sunlight can be reflected more effectively, which can improve heat insulation performance.
[0261] In order to realize a low refractive index, a resin having a low refractive index or particles having a low refractive index may be used.
[0262] The resin with low refractive index can be a resin with a refractive index of less than 1.6, such as a silicone resin, a fluororesin or a resin containing a fluorine group. Examples of the types of silicone resins include methyl, methyl / phenyl, propyl / phenyl, epoxy-modified, alkyd-modified, polyester-modified, rubber, and resins and oligomers thereof. These resins can be used alone or in combination of two or more.
[0263] By dispersing particles with a particle size of less than 100 nm and a refractive index of 1.6 or less (referred to as "low refractive index particles") in the resin, the refractive index of the resin region can be reduced. Alternatively, particles with a low refractive index can be dispersed in a resin with a low refractive index.
[0264] The low refractive index particles may be organic particles or inorganic particles. The low refractive index particles may contain, for example, fluorine, MgF 2 The low refractive index particles may have a spherical shape or an amorphous shape, and may be hollow or porous particles.
[0265] The content of the resin with a low refractive index according to the embodiment is preferably 20% by volume or more and 100% by volume or less, and more preferably 30% by volume or more and 90% by volume or less. If the content of the resin according to the embodiment of the present invention is less than 20% by volume, the adhesion of the resin region 123 to the particle region 124 adjacent to the resin region 123 may be deteriorated. Similarly, if the content of the resin with a low refractive index according to the embodiment is greater than 90% by volume, the adhesion of the resin region 123 to the particle region 124 adjacent to the resin region 123 may be deteriorated.
[0266] The shape and area of the resin region 123 can be determined by performing typical SEM observation on a film cross section perpendicular to the surface 1220 of the film 122. The SEM observation is performed at an accelerating voltage of 5 kV and at a magnification of 1000 times.
[0267] The width D of the resin region 123 in the direction perpendicular to the surface of the substrate 120 is preferably 200 nm or more and 2000 nm or less, and more preferably 200 nm or more and 1000 nm or less. If the width D of the resin region 123 in the direction perpendicular to the surface of the substrate 120 is less than 200 nm, the resin region 123 may not contribute to water resistance. If the width D is greater than 2000 nm, the heat insulation performance may deteriorate.
[0268] The width E of the resin region 123 in the direction parallel to the surface of the substrate 120 is preferably 3 μm or more and 100 μm or less, and more preferably 5 μm or more and 50 μm or less. If the width E is 3 μm or less, the resin region 123 may not contribute to water resistance. If the width E is greater than 100 μm, defects such as film separation may be caused.
[0269] The total area of the resin regions 123 distributed in the film 122 is preferably 0.05 area% or more and 13 area% or less, and more preferably 0.1 area% or more and 5 area% or less relative to the entire cross-sectional area of the film. If the total area is less than 0.05 area%, the resin regions 123 may not contribute to water resistance. If the total area is greater than 13 area%, the thermal insulation performance may be significantly deteriorated.
[0270] Membrane configuration
[0271] The film formed on the article according to this embodiment, particularly the film formed on the upper surface of the optical device, is formed on the outer side relative to the substrate. The film may be closely adhered to the substrate, or a primer layer for improving adhesion may be provided between the substrate and the film formed on the upper surface of the optical device. When a metal substrate is used, a chemical conversion treatment may be optionally performed.
[0272] The substrate may be formed of any material, such as metal or plastic. Examples of metals include aluminum, titanium, stainless steel, magnesium alloys, and lithium-magnesium alloys. Examples of plastics include polycarbonate resins, acrylic resins, ABS resins, and fluororesins.
[0273] The substrate may have any thickness. The thickness is preferably 0.5 mm or more and 5 mm or less, more preferably 0.5 mm or more and 2 mm or less. If the thickness is less than 0.5 mm, it is difficult to maintain the shape of the lens barrel. If the thickness is greater than 5 mm, the cost of the component increases.
[0274] Primer
[0275] Primers can be used to improve the adhesion between the substrate and the film.
[0276] The primer may be formed of any material. Examples of the material include epoxy resins, polyurethane resins, acrylic resins, silicone resins, and fluororesins. The primer may contain particles according to an embodiment of the present invention, particles other than particles according to an embodiment of the present invention, colorants, dispersants, curing agents, curing catalysts, plasticizers, thixotropy-imparting agents, leveling agents, organic colorants, inorganic colorants, preservatives, ultraviolet light absorbers, antioxidants, coupling agents, and solvent residues.
[0277] The thickness of the primer is preferably 2 μm or more and 30 μm or less, and more preferably 5 μm or more and 20 μm or less. If the thickness is less than 2 μm, the adhesion of the film is sometimes reduced. If the thickness exceeds 30 μm, the positioning accuracy may be adversely affected.
[0278] The film thickness according to this embodiment
[0279] The thickness of the film according to this embodiment can be set to 10 μm or more and 70 μm or less. If the thickness is less than 10 μm, the solar reflectivity may be deteriorated. If the thickness is greater than 70 μm, the center may be offset during assembly with other components, which may adversely affect the positioning accuracy of the optical device.
[0280] Method for manufacturing an article according to the embodiment
[0281] Film forming method
[0282] The film of the article according to this embodiment may be formed by any coating method and any curing method as long as the heat-insulating coating material according to this embodiment can be uniformly coated to have a thickness of 10 μm or more and 70 μm or less.
[0283] Examples of coating methods for the film of the article (particularly for optical devices) according to the embodiment include brushing, spraying, dipping, transfer and inkjet coating. The film can be composed of a single coating or multiple coatings, or can be granulated to achieve a good design.
[0284] The curing method of the film for the article (particularly for optical equipment) according to this embodiment may be a method of leaving the coating at room temperature, a method of promoting curing by any heating process, or a method of applying ultraviolet rays. In the method of curing by a heating process, for example, a heating furnace, a heater or infrared heating may be used. The curing temperature is preferably room temperature to 400°C, and more preferably room temperature to 200°C.
[0285] Method of forming resin region
[0286] After forming the film (particle region) by the above method, the material for the resin region can be applied to a portion of the surface of the film (particle region) by a method such as transfer or inkjet coating to form the resin region. By further forming the film (particle region) after forming the resin region, a resin region can be formed inside the film (between the particle region and the particle region). When the substrate is flat, the resin region can also be formed by using photolithography. The method for curing the linear region (between the particle region and the particle region) in the film for optical devices according to an embodiment of the present invention can be a method of placing the material at room temperature, a method of promoting curing by any heating process, or a method of applying ultraviolet rays. In the method of curing by a heating process, for example, a heating furnace, a heater or infrared heating can be used. The curing temperature is preferably room temperature to 400°C, and more preferably room temperature to 200°C.
[0287] Example
[0288] Hereinafter, suitable embodiments of the present invention will be described.
[0289] Evaluation of film characteristics and formation of films in Examples 14 to 27 were performed by the following methods.
[0290] Evaluation of water resistance of thermal insulation films
[0291] Water resistance testing and evaluation
[0292] The film according to this embodiment was formed on a metal plate having a size of 30 mm × 30 mm and a thickness of 1 mm to prepare a sample for measuring water resistance. The metal plate was formed of stainless steel, aluminum, titanium or a magnesium alloy. The coating was applied to a metal plate formed of a magnesium alloy by using a spin coater and inkjet coating to have a thickness of 65 μm and fired to form a film.
[0293] The thermal insulation film according to this embodiment was inserted into a thermostat of high temperature and high humidity (temperature: 70° C., humidity: 90%) for 100 hours to investigate water resistance.
[0294] By comparing the results before and after the water resistance test, the water resistance was evaluated according to JIS K5600-5-4 (scratch hardness (pencil method)). When the hardness did not change before and after the water resistance test, an evaluation result of "A" was given. When the hardness decreased after the water resistance test, an evaluation result of "B" was given.
[0295] Evaluation of solar reflectance
[0296] The solar reflectance was determined by using the same instrument and method as in the first embodiment.
[0297] A film was formed on a metal plate having a size of 30 mm×30 mm and a thickness of 1 mm to prepare a sample for measurement. The metal plate was formed of stainless steel, aluminum, titanium or a magnesium alloy. The coating was applied to the metal plate formed of a magnesium alloy using a spin coater and inkjet coating to have a thickness of 65 μm and fired to form a film.
[0298] When the solar reflectance is 70% or more, the film is an excellent film because the cooling effect is high. When the solar reflectance is 60% or more and less than 70%, the film is a good film because the cooling effect is relatively high. When the solar reflectance is less than 60%, the film is a poor film because the cooling effect is reduced.
[0299] Three-level evaluation A to C
[0300] A: Solar reflectance is 70% or more.
[0301] B: The solar reflectance is 60% or more and less than 70%.
[0302] C: Solar reflectivity is less than 60%
[0303] Thermal insulation effect
[0304] The thermal insulation effect was also determined by using the same instrument and method as in the first embodiment.
[0305] Embodiment 14
[0306] Coating preparation
[0307] In Example 14, a coating material was prepared by the following method. That is, 15 g of titanium oxide (20% by volume based on the coating film), 13 g of resin (57.5% by volume based on the coating film), 0.75 g of silica (1.8% by volume based on the coating film), 1 g of pigment (3.5% by volume based on the coating film), 3.9 g of curing agent (17.2% by volume based on the coating film) and 3 g of diluent were weighed and stirred using a planetary mixer (AR-100, THINKY Corporation) for 10 minutes to prepare coating material T1 in Example 14. The titanium oxide used was D-970 (SAKAI CHEMICAL INDUSTRY Co., Ltd., average particle size 0.26 μm, silica-coated surface). The resin used was Olester Q-691 (Mitsui Chemicals, Inc.).
[0308] The silica particles used were AEROSIL R-972 (NIPPON AEROSIL Co., Ltd., average particle size 100 nm). The pigment used was CHROMOFINE BLACK A1103 (Dainichiseika Color & Chemicals Mfg. Co., Ltd.). The curing agent used was Takenate D-120N (Mitsui Chemicals, Inc.).
[0309] The coating material T2 used to form the resin region 123 in Example 14 was prepared by weighing 0.75 g of silica, 13 g of resin, 3.9 g of curing agent, and 20 g of diluent and stirring the mixture for 10 minutes using a planetary mixer (AR-100, THINKY Corporation). The resin used was Olester Q-691 (Mitsui Chemicals, Inc.). The silica used was AEROSIL R-972 (NIPPON AEROSIL Co., Ltd., average particle size 100 nm). The curing agent used was Takenate D-120N (Mitsui Chemicals, Inc.).
[0310] Formation of thermal insulation film
[0311] In Example 14, two samples having films formed thereon were prepared by the following method.
[0312] First, the coating T1 was applied to a metal plate formed of a magnesium alloy using a spin coater to have a thickness of 20 μm, dried at room temperature overnight, and then fired at 130°C for 30 minutes to form a film M1. Then, the coating T2 was applied to the surface of the film M1 by pad printing to have a pattern having a size of 10 μm×8 μm and a thickness of 1.5 μm. Subsequently, it was dried at room temperature overnight and then fired at 130°C for 30 minutes to form a resin region 123. Subsequently, the coating T1 was applied using a spin coater to have a thickness of 45 μm, dried at room temperature overnight, and then fired at 130°C for 30 minutes to obtain two samples in Example 14. A cross section of one of the two samples was cut out and observed. The area ratio of the resin region 123 relative to the entire area of the film cross section was 0.15 area%.
[0313] Examples 15 to 27
[0314] In Examples 15 to 27, coating materials and samples having films formed thereon were prepared in the same manner as in Example 14, except that the materials and conditions listed in Table 7 were used.
[0315] Comparative Examples 3 to 12
[0316] In Comparative Examples 3 to 12, coating materials and samples having films formed thereon were prepared in the same manner as in Example 14, except that the materials and conditions listed in Table 7 were used.
[0317] For these films, the change in scratch hardness after the water resistance test, the solar reflectance after the water resistance test, and the cooling effect before and after the light resistance test were evaluated in the same manner as in Examples 14 to 27.
[0318] Table 7
[0319]
[0320]
[0321] Evaluation results
[0322] Table 8 shows the change in scratch hardness after the water resistance test, the solar reflectance after the water resistance test, the cooling effect before and after the light resistance test, and the optical accuracy evaluated by the above method for the films in Examples 14 to 27 and Comparative Examples 3 to 12. For the optical accuracy, an evaluation result of "A" is given when the axis offset is tolerable, and an evaluation result of "B" is given when the axis offset is not tolerable.
[0323] Table 8
[0324]
[0325] Third embodiment
[0326] In this embodiment, an article including a single-layer film satisfying both design and heat insulation performance will be described. The same description as in the first embodiment may be omitted.
[0327] Methods to meet design and insulation performance
[0328] Methods for ensuring the design of the exterior color
[0329] Usually, in order to ensure the design of the appearance color of articles such as lens barrels, for example, a film with the desired color adjusted by a colorant is formed on a substrate. However, if the film has a dark color, the film needs to contain a large amount of dark colorants. If the film contains a large amount of dark colorants, a large amount of visible light will be absorbed, which will increase the temperature through sunlight and deteriorate the thermal insulation performance. In this embodiment, an organic pigment is used as a dark colorant, and the amount of the organic pigment distributed on the air interface side is greater than the amount distributed on the substrate side of the film. Therefore, even if the content of the organic pigment is reduced, a film with a desired color can be obtained. In order to distribute a larger amount of organic pigments on the air interface side than on the substrate side of the film, the organic pigments contained in the film are only intentionally aggregated. It has been found that by segregating the aggregated organic pigments only on the air interface side of the film by convection during film formation, even if the content of the dark component is low, the color can be adjusted to the desired color. For this reason, a coating containing at least resin, organic pigment, inorganic pigment and dispersant is applied to the substrate to form a film. The dispersant used is a dispersant that can aggregate organic pigments instead of inorganic pigments. For example, an alkanolammonium salt is used as a dispersant. Therefore, only the organic pigment can be aggregated, and the organic pigment can be segregated on the air interface side.
[0330] Methods for ensuring thermal insulation performance
[0331] In order to ensure the heat insulation performance of an object such as a lens barrel, it is necessary to reflect infrared rays in sunlight. Figure 1 is a schematic cross-sectional view illustrating reflection and absorption of sunlight on the film according to this embodiment. Figure 1 The incident light 1, reflected light 2, transmitted light 3, film 4 and substrate 5 are shown. The wavelength of sunlight is in the range of about 0.3 μm to about 3 μm. Figure 1 When light having such a wavelength becomes transmitted light 3, the energy is converted into heat energy, so that the substrate 5 generates heat. Therefore, in order to suppress the generation of heat due to sunlight without using a heat insulating layer, it is necessary to suppress the heat generated by the transmission of light to the inside by increasing the ratio of reflected light 2 to incident light 1 as much as possible.
[0332] For particles with a particle size of several microns, the wavelength range of sunlight from 0.3 μm to 3 μm is the Mie scattering region. Based on the calculation of Mie scattering, the highest reflectivity of sunlight is achieved at a particle size of about 1 μm. Therefore, the particle size of sunlight reflective particles is generally about 1 μm.
[0333] In order to more effectively reflect infrared rays by the sunlight reflecting particles, it is desirable that the reflecting particles are uniformly dispersed in the film 4. Uneven dispersion of the reflecting particles deteriorates the temperature lowering effect.
[0334] The sunlight reflecting particles are, for example, colored inorganic pigment particles, such as white titanium dioxide particles. By uniformly dispersing the inorganic pigment particles in the film, sufficient infrared reflection can be achieved.
[0335] A method to satisfy both design and thermal insulation performance
[0336] In this embodiment, the design of the appearance color of the lens barrel and the heat insulation performance are ensured by the following method. The design is ensured by adjusting the color to the desired color only on the surface of the film through the segregation of the organic pigment to the air interface side. In addition, by uniformly dispersing titanium dioxide particles or infrared reflective colored inorganic pigment particles in the interior (from the center part toward the interface with the substrate) except the surface part of the film, infrared rays are effectively reflected and thus the heat insulation performance is ensured.
[0337] Figure 8 is a schematic cross-sectional view illustrating the film according to this embodiment. Figure 8 The cross section of the film shown in is a cross section having a width W and extending from the air interface 221 to the substrate 205 in the thickness direction (A direction), and the cross section is cut out from the article on which the film is formed in a direction parallel to the perpendicular direction of the film surface. Figure 8 An air interface 221 of the film 204, a substrate interface 222 of the film 204, a resin 223, an organic pigment 224, and an inorganic pigment 225 are shown. In this embodiment, 221 represents an air interface because the surface of the film 204 is in contact with the air. However, even if another film is formed on the film 204, the interface between the film 204 and the other film is also referred to as an air interface in this embodiment. When the resin region described in the second embodiment is formed in the film, a cross section is cut from the air interface 21 to the resin region in the thickness direction (direction A). As shown in FIG. Figure 8As shown, the cross section is divided into 10 parts (air interface side: 1 and substrate side: 10) in the thickness direction A. It has been found that, assuming that the content of organic pigments in the cross section is 100% by area, when 70% by area or more and 95% by area or less of the organic pigments are distributed in the 1st to 3rd parts in the thickness direction, both the design and the heat insulation performance can be met. In other words, it has been found that when the area of 30% of the cross section cut from the air interface of the film toward the substrate interface in the thickness direction contains 70% by area or more and 95% by area or less of the organic pigments, both of them can be met. In this embodiment, the content of the organic pigment 224 is measured by the following method. First, the cross section of the film is cut out at five locations. Each cross section of the film is cut out in a direction parallel to the direction perpendicular to the film surface to have a width W (e.g., 1 μm). The direction perpendicular to the film surface refers to the direction perpendicular to the surface obtained by connecting the protrusions when the film surface has protrusions and depressions. The cross sections at five locations are magnified 100,000 times by a transmission electron microscope (TEM). Then, the particles are analyzed regionally at five locations by energy dispersive X-ray spectroscopy (EDS) to calculate the content per unit area. Finally, the content of the organic pigment 224 in the film 204 according to an embodiment of the present invention is calculated by the average value of the content at the five locations. In this embodiment, the content calculated by this method is expressed in area % units.
[0338] That is, for example, when it is assumed that the cut cross section is 100 area%, an organic pigment of 0.1 area% or more and 2.0 area% or less is contained in the film 204. In this case, when the organic pigment 224 of 70 area% or more and 95 area% or less is contained in the 1st to 3rd parts starting from the air interface of the film 204, both the design and the heat insulation performance can be satisfied. The 1st to 3rd parts starting from the air interface of the film 204 refer to the area extending 30% of the length from the air interface toward the substrate when it is assumed that the length from the air interface to the substrate of the film 204 is 100%. When it is less than 70 area%, a larger amount of organic pigment 224 needs to be added to ensure the design of the appearance color, which deteriorates the heat insulation performance. When it is greater than 95 area%, an interface is formed in the 1st to 3rd parts starting from the air interface of the film (i.e., 30% from the air interface in the thickness direction), and infrared rays enter the film through undesirable interface reflection, which inhibits the cooling effect. The 1st to 3rd parts starting from the air interface of the film refer to the area from the air interface of the film to the line located at 30% of the length and parallel to the substrate when the length of the cut-out cross section of the film from the air interface to the substrate is assumed to be 100%. In this embodiment, the length from the air interface to the substrate refers to the length from the interface of the film on the air interface side to the substrate or the length from the interface on the air interface side to the resin region. When the cut-out cross section of the film has projections and depressions on the air interface side, the line extending along the most depressed part (wherein the length from the air interface of the cut-out cross section of the film to the substrate (or resin region) is the smallest part) and parallel to the substrate is defined as the interface of the film on the air interface side.
[0339] Coating according to this embodiment
[0340] Hereinafter, a material for coating according to this embodiment and a method for preparing coating according to an embodiment of the present invention will be described.
[0341] Material
[0342] The coating material according to this embodiment contains at least a resin, an organic pigment, an inorganic pigment, and a dispersant.
[0343] Resin composition
[0344] The resin contained in the coating material according to this embodiment will be described.
[0345] Examples of the resin according to this embodiment include epoxy resins, polyurethane resins, acrylic resins, polyurethane-acrylic resins, phenolic resins, and alkyd resins. These resins may be used alone or in combination of two or more.
[0346] When the total amount of the coating is assumed to be 100wt%, the content of the resin in the coating according to this embodiment is preferably 5wt% or more and 80wt% or less, and more preferably 15wt% or more and 50wt% or less. If the content of the resin in the coating according to this embodiment is less than 5wt%, the adhesion to the substrate or the toughness of the film may deteriorate. If the content of the resin in the coating according to this embodiment is greater than 50wt%, the solar reflectance may deteriorate. The coating is mainly composed of a solvent component volatilized during the formation of the coating film and a resin component and a pigment remaining in the coating film. Therefore, after drying and firing the coating under specific conditions, the content of the resin component or the pigment in the coating is determined as the solid content.
[0347] Organic Pigments
[0348] The organic pigment contained in the coating material according to this embodiment is an azo-based organic pigment or a perylene pigment.
[0349] The azo organic particles may be any particles as long as they are particles of a compound having an azo group. Examples of the color of the azo organic particles according to this embodiment include black colors, yellow colors, red colors, and orange colors. Black colors may be used because the color tone (a * and b * ) changes little. The solar reflectance can be set high, and a material whose solar reflectance is greater than 10% achieved only by azo organic particles can be selected. Examples of azo organic particles include particles of nickel azo pigments, insoluble azo pigments, soluble azo pigments, high molecular weight azo pigments, and azomethine azo pigments. These azo organic particles can be used alone or in combination of two or more.
[0350] The average particle size of the organic pigment according to this embodiment is preferably 0.1 μm or more and 5.0 μm or less, and more preferably 0.1 μm or more and 2.0 μm or less. If the average particle size of the organic pigment according to this embodiment is less than 0.1 μm, the surface area of the particles increases. Therefore, the light resistance deteriorates, which may cause discoloration. If the average particle size of the organic pigment according to this embodiment is greater than 5.0 μm, the irregularity of the coating film increases and the thickness accuracy deteriorates. Therefore, when this embodiment is applied to a lens barrel, the focusing accuracy, etc. may deteriorate.
[0351] The average particle size in this embodiment is the average value of the particle sizes of a plurality of resin particles. The average particle size of the resin particles is determined by dispersing the particles in water and analyzing them by laser scattering. In this embodiment, the average particle size of the resin particles is the volume average particle size.
[0352] The average particle diameter of the organic pigment according to this embodiment may be set larger than that of an inorganic pigment described later in order to easily cause segregation to the air interface side due to aggregation of the organic pigment.
[0353] The organic pigment may be particles having any shape. Examples of the shape include sphere, cube, ellipse, plate, layer, chain, hollow, star, needle, and special shape. In particular, for example, plate, layer, and chain that easily cause phase-air interface side segregation due to aggregation of the organic pigment may be used.
[0354] These organic pigments may be used alone or in combination of two or more as long as the design and heat insulation performance are not impaired.
[0355] When the total amount of the coating is assumed to be 100 wt%, the content of the organic pigment in the coating according to this embodiment is preferably 0.01 wt% or more and 1.0 wt% or less, and more preferably 0.015 wt% or more and 0.5 wt% or less. If the content of the organic pigment is less than 0.01 wt%, the brightness of the film is excessively increased, which may deteriorate the design and may also deteriorate the antifouling performance. If the content of the organic pigment is 1.0 wt% or more, the brightness of the film is excessively reduced, which deteriorates the heat insulation performance.
[0356] Inorganic Pigments
[0357] The inorganic pigment used in this embodiment can be any inorganic pigment, as long as the inorganic pigment has good heat insulation performance, and can contain the titanium dioxide particles whose surface is coated with silicon dioxide.Especially, the inorganic pigment also contains the colored inorganic pigment for adjusting the color.The inorganic pigment can contain the particles containing Ti and O that are not coated on its surface.The particles containing Ti and O that are not coated on its surface can be colored inorganic pigment.In this embodiment, the particles containing Ti and O that are not coated on its surface can be referred to as particles containing Ti and O.
[0358] Since titanium dioxide itself has a high refractive index, the refractive index of the film can be easily adjusted to a desired refractive index. Due to the bright color of titanium dioxide itself, the color tone of the coating film can also be easily adjusted to a desired color tone. In addition, a large amount of titanium dioxide products of sufficiently fine particles can be commercially obtained at a relatively low cost, so titanium dioxide can be appropriately used.
[0359] The content of the titanium dioxide particles whose surfaces are coated with silicon dioxide in the film according to this embodiment is preferably 10wt% or more and 70wt% or less, and more preferably 20wt% or more and 60wt% or less relative to the resin composition. If the content is less than 10wt%, the infrared reflection effect may not be sufficiently produced. If the content is greater than 70wt%, sufficient film quality may not be obtained. When particles whose surfaces are coated with silicon dioxide are used, photocatalytic activity may be suppressed, which may suppress the degradation of surrounding resins.
[0360] The average particle size of the titanium dioxide particles whose surfaces are coated with silica according to this embodiment is preferably 0.1 μm or more and 1.5 μm or less, more preferably 0.1 μm or more and 1.0 μm or less. If the average particle size is less than 0.1 μm, the surface area of the particles increases, and the titanium dioxide particles whose surfaces are coated with silica are prone to aggregation, which makes it difficult to properly disperse the titanium dioxide particles in the film. Although described in detail later, if the average particle size is greater than 1.5 μm, the segregation of the organic pigment to the air interface side is suppressed, and the design and thermal insulation performance cannot be fully achieved. The titanium dioxide particles whose surfaces are coated with silica according to this embodiment are defined as particles in which at least a portion of the surface is coated with silica. The average particle size of the titanium dioxide particles whose surfaces are coated with silica according to this embodiment represents the equivalent spherical diameter of the particles that are not aggregated.
[0361] Titanium dioxide particles coated with silicon dioxide on their surfaces according to this embodiment can be prepared by a known method such as a gas phase method or a liquid phase method, as long as the required refractive index and the required average particle size are met. Examples of the method include a method in which a metal powder is charged into a flame and burned in an atmosphere containing at least oxygen to synthesize titanium dioxide fine particles and a sol-gel method in which titanium alkoxide is hydrolyzed and polycondensed in the presence of a catalyst. Titanium dioxide is known to have a crystalline structure, such as a rutile structure or anatase structure, which exhibits a higher refractive index than an amorphous structure. However, as long as the required particle size is met, titanium dioxide having any crystalline form can be suitably used.
[0362] In addition to the titanium dioxide particles whose surface is coated with silicon dioxide, the inorganic pigment according to this embodiment may contain colored inorganic pigments. The content of the infrared reflective colored inorganic pigment according to this embodiment is preferably 0.01% by weight or more and 2.0% by weight or less, more preferably 0.02% by weight or more and 1.5% by weight or less. If the content of the infrared reflective colored inorganic pigment according to this embodiment is less than 0.01wt%, the photocatalytic effect during irradiation with sunlight is low, which may significantly change the appearance tone of the film according to this embodiment. If the content of the infrared reflective colored inorganic pigment according to this embodiment is greater than 2.0wt%, the thermal insulation performance may deteriorate. The infrared reflective colored inorganic pigment according to this embodiment can be uniformly dispersed in the film.
[0363] The inorganic pigment according to this embodiment may further contain particles containing Ti and O whose surfaces are not coated. The particles containing Ti and O are hardly coated with or not coated with silica or the like having light resistance, because the molecular chains of the resin need to be cracked by photocatalysis. This is because the brightness of the film is reduced during irradiation with sunlight by using the photocatalytic effect of the particles containing Ti and O whose surfaces are not coated. The reasons are as follows. The azo-based organic particles used as organic pigments are colored pigments having a chemical structure of an azo group RN=N-R' in the molecule. The azo-based organic particles have a higher infrared reflectivity than inorganic pigments. However, when the azo-based organic particles are irradiated with sunlight, the azo group is cracked into 2R and N 2 . Azo-based organic particles show color by the N=N contained therein and the surrounding atomic arrangement. Therefore, if N=N is cleaved, the color disappears, which increases the brightness. That is, the color of the film formed on the surface of an item such as an optical device can change significantly. This change appears significantly when the content of the azo-based organic particles decreases.
[0364] Due to sunlight, TiO in the Ti and O-containing particles 10 2 The Ti and O-containing particles excited by sunlight transfer electrons (e - ) is released into the resin, and the molecular chains of the resin are cleaved by the electron energy. As a result, the resin becomes a discolored resin, so the brightness decreases.
[0365] In the film according to the embodiment of the present invention, the brightness of the azo organic particles increases due to irradiation with sunlight, while the brightness of the particles containing Ti and O decreases. In general, the offset effect suppresses discoloration. The particles containing Ti and O include particles containing only Ti and O (e.g., titanium dioxide particles) and / or particles containing at least one inorganic metal in addition to Ti and O. Examples of particles containing at least one inorganic metal in addition to Ti and O according to this embodiment include (Ti, Ni, Sb) Ox, (Ti, Cr, Sb) Ox, (Ti, Fe, Zn) Ox, (Co, Cr, Zn, Al, Ti) Ox, (Co, Cr, Zn, Ti) Ox, and (Co, Al, Ni, Ti) Ox. Examples of particles containing Ti and O according to an embodiment of the present invention include (Ti, Ni, Sb) Ox, (Ti, Cr, Sb) Ox, (Ti, Fe, Zn) Ox, (Co, Cr, Zn, Al, Ti) Ox, (Co, Cr, Zn, Ti) Ox, and (Co, Al, Ni, Ti) Ox. When particles containing Ti and O are contained, the content may be set to 1.6 wt% or less.
[0366] Silica particles
[0367] In this embodiment, silica particles may be further included. The average particle size of the silica particles may be set to be greater than 10nm and less than 110nm. When the average particle size is within the range of greater than 10nm and less than 110nm, the micro defects of the silica on the surface of the titanium dioxide particles can be filled, which suppresses discoloration in an oxygen-free atmosphere. If the average particle size of the silica particles according to this embodiment is less than 10nm, the micro defects of the silica on the surface of the titanium oxide particles are not easily filled, which may make it difficult to suppress discoloration in an oxygen-free atmosphere. If the average particle size of the silica particles included in the coating according to an embodiment of the present invention is greater than 110nm, the adsorption of titanium oxide is deteriorated, which may make it difficult to suppress discoloration in an oxygen-free atmosphere.
[0368] The silica particles may have any shape. Examples of the shape of the silica particles include spherical, amorphous, star-shaped, chain-shaped, hollow, and porous. These silica particles may be used alone or in combination of two or more.
[0369] The particle size of the silica particles 128 according to this embodiment is a number average particle size. Before applying the coating, the average particle size of the silica particles 128 can be measured by a dynamic light scattering method. When the average particle size is measured after the film is formed, a sample with a thickness of 300 nm and a size of 5 μm×5 μm is cut out at 5 locations from the film according to this embodiment, and magnified 100,000 times by a transmission electron microscope (TEM). Then, the silica particles 128 are regionally analyzed at five locations by energy dispersive X-ray spectroscopy (EDS) to determine the particle size of the silica particles 128 and calculate the average value of the particle size. Finally, the average value of the particle size at the five locations is determined. The average value of the particle size at the five locations is defined as the average particle size of the silica particles contained in the film according to this embodiment. In this embodiment, for example, when silica particles 128 having a particle size of 10 nm or more and 50 nm or less aggregate to form secondary particles, such as Figure 7C As shown, when the length of the secondary particles in the long side direction is 50 nm or more and 350 nm or less, the coating performance can be improved. In particular, branched silica particles consisting of chains of spherical silica particles 128 can be selected. When applying a coating for forming a light-shielding film, branched silica particles consisting of chains of spherical silica particles 128 are suitable because the space formed by the silica particles 128 increases, so the particles 127 can easily move.
[0370] Relative to the non-volatile components in the coating, the content of the silica particles is 0.6% by mass or more and 14% by mass or less, and preferably 1% by mass or more and 10% by mass or less. If the content of the silica particles is less than 0.6% by mass, the micro defects of the silica coated with the titanium oxide particles cannot be completely filled, which may further lead to discoloration in an oxygen-free atmosphere. If the content of the silica particles according to an embodiment of the present invention is greater than 14% by mass, the haze of the coating film deteriorates, which may deteriorate the reflectivity. The content of the silica particles relative to the non-volatile components in the coating can be determined by the same method as the content of the silica particles in the film according to the embodiment of the present invention after the coating is cured. The method will be described later.
[0371] Dispersants
[0372] The dispersant included in the coating according to this embodiment can be any dispersant, as long as the dispersant can aggregate organic pigments instead of inorganic pigments. In particular, the dispersant contains an alkanolammonium salt. Initially, the dispersant is adsorbed on the surface of the pigment particles so that the pigment particles maintain a constant distance from each other, thereby preventing the aggregation between the pigment particles. However, the dispersant in this embodiment aggregates organic pigments and disperses inorganic pigments.
[0373] The dispersant according to an embodiment of the present invention may include at least one acidic group. The dispersant according to an embodiment of the present invention may have an acid value (mgKOH / g) of 30 or more and 100 or less. When the acid value (mgKOH / g) is 30 or more and 100 or less, the organic pigment may be more appropriately precipitated on the air interface side. The amount of the added dispersant may be greater than the amount of the organic pigment. If the amount of the added dispersant is less than the amount of the organic pigment, the organic pigment is partially dispersed, which reduces the amount of the organic pigment segregated on the air interface side.
[0374] The content of the dispersant in the coating according to an embodiment of the present invention is preferably 0.1 wt % or more and 10.0 wt % or less and more preferably 0.15 wt % or more and 7.0 wt % or less. If the content of the dispersant is less than 0.1 wt %, the heat insulation performance is deteriorated. If the content of the dispersant is 10.0 wt % or more, the refractive index of the layer is reduced, which reduces the reflection caused by the refractive index difference.
[0375] Solvents
[0376] The solvent contained in the coating material will be described.
[0377] Any solvent can be used. Examples of solvents include water, diluents, ethanol, isopropanol, n-butanol, ethyl acetate, propyl acetate, isobutyl acetate, butyl acetate, and methyl ethyl ketone. Other examples of solvents include methyl isobutyl ketone, propylene glycol monomethyl ether, toluene, xylene, acetone, cellosolve, glycol ether, and ether. These solvents can be used alone or in combination of two or more.
[0378] The viscosity of the coating according to the embodiment of the present invention is preferably 10 mPa·s or more and 10000 mPa·s or less, and more preferably 20 mPa·s or more and 1000 mPa·s or less. If the viscosity of the coating is less than 10 mPa·s, the thickness of the applied thermal insulation film may be reduced in some places. If the viscosity of the coating is greater than 10000 mPa·s, the coating performance of the coating may deteriorate.
[0379] Other additives
[0380] The coating material for the optical device according to the embodiment may contain any other additives. Examples of the additives include a curing agent, a curing catalyst, a plasticizer, a thixotropy-imparting agent, a leveling agent, a matting agent, a preservative, an ultraviolet absorber, an antioxidant, and a coupling agent.
[0381] Method for preparing coating
[0382] Hereinafter, a method for preparing a coating material according to this embodiment will be described.
[0383] The method for preparing the coating for forming a film on the upper surface of the optical device according to the embodiment may be any method as long as the organic particles and inorganic pigments according to the embodiment of the present invention can be dispersed in the coating. For example, a bead mill, a ball mill, a jet mill, a three-roll mixer, a planetary mixer, a mixer, an ultrasonic disperser or a homogenizer may be used.
[0384] membrane
[0385] Hereinafter, materials used for the film according to this embodiment will be described.
[0386] The film according to this embodiment contains at least a resin, an organic pigment, and an inorganic pigment.
[0387] Material
[0388] Resin composition
[0389] The content of the resin according to this embodiment is preferably 20 area % or more and 90 area % or less, more preferably 30 area % or more and 80 area % or less. If the content of the resin according to this embodiment is less than 20 area %, the adhesion to the substrate may be deteriorated. If the content of the resin according to this embodiment is greater than 90 area %, the solar reflectance may be deteriorated.
[0390] Organic Pigments
[0391] The content of the organic pigment according to the embodiment of the present invention is preferably 0.1 area % or more and 2.0 area % or less, and more preferably 0.15 area % or more and 1.5 area % or less. If the content of the organic pigment is less than 0.1 area %, the brightness of the film is excessively increased, which may deteriorate the design and may also deteriorate the antifouling performance. If the content of the organic pigment is 2.0 area % or more, the brightness of the film is excessively reduced, which may deteriorate the heat insulation performance.
[0392] Inorganic Pigments
[0393] The content of the titanium dioxide particles whose surface is coated with silicon dioxide and used as an example of the inorganic pigment for adjusting brightness according to this embodiment is preferably 10 area % or more and 80 area % or less, more preferably 20 area % or more and 60 area % or less. If the content of the inorganic pigment for adjusting brightness according to this embodiment is less than 10 area %, the tinting strength is low, which may make it difficult to adjust the brightness to 50 or more. If the content of the inorganic pigment for adjusting brightness according to this embodiment is more than 80 area %, the film may become brittle.
[0394] The content of the colored inorganic pigment according to this embodiment is preferably 0.1 area % or more and 3.0 area % or less, more preferably 0.2 area % or more and 2.0 area % or less. If the content of the colored inorganic pigment according to this embodiment is less than 0.1 area %, the photocatalytic effect during irradiation with sunlight is low, which may significantly change the appearance color tone of the film. If the content of the colored inorganic pigment is greater than 3.0 area %, the heat insulation performance may deteriorate.
[0395] Colored inorganic pigments can be uniformly dispersed in the film.
[0396] Other additives
[0397] The coating material for the optical device according to the embodiment may contain any other additives. Examples of the additives include a curing agent, a curing catalyst, a plasticizer, a thixotropy-imparting agent, a leveling agent, a matting agent, a preservative, an ultraviolet absorber, an antioxidant, and a coupling agent.
[0398] Membrane configuration
[0399] The film formed on the upper surface of the optical device according to this embodiment is formed on the outer side relative to the substrate. The film may be closely adhered to the substrate, or a primer layer for improving adhesion may be provided between the substrate and the film formed on the upper surface of the optical device.
[0400] Substrate
[0401] The substrate may be formed of any material, such as metal or plastic. Examples of metals include aluminum, titanium, stainless steel, magnesium alloys, and lithium-magnesium alloys. Examples of plastics include polycarbonate resins, acrylic resins, ABS resins, and fluororesins.
[0402] The substrate may have any thickness. The thickness is preferably 0.5 mm or more and 5 mm or less, more preferably 0.5 mm or more and 2 mm or less. If the thickness is less than 0.5 mm, it is difficult to maintain the shape of the lens barrel. If the thickness is greater than 5 mm, the cost of the component increases.
[0403] Primer
[0404] Primer can be used to improve the adhesion between substrate and film. In this specification, when primer is used, the substrate and the primer on the substrate are referred to as substrate. That is, the substrate includes the primer.
[0405] The primer may be formed of any material. Examples of the material include epoxy resins, polyurethane resins, acrylic resins, silicone resins, and fluororesins. The primer may contain particles according to the embodiment, particles other than the particles according to the embodiment, colorants, dispersants, curing agents, curing catalysts, plasticizers, thixotropy-imparting agents, leveling agents, organic colorants, inorganic colorants, preservatives, ultraviolet absorbers, antioxidants, coupling agents, and solvent residues.
[0406] The thickness of the primer is preferably 2 μm or more and 30 μm or less, and more preferably 5 μm or more and 20 μm or less. If the thickness is less than 2 μm, the adhesion of the film is sometimes reduced. If the thickness exceeds 30 μm, the positioning accuracy may be adversely affected.
[0407] The film thickness according to this embodiment
[0408] The thickness of the film according to this embodiment is preferably 10 μm or more and 100 μm or less, more preferably 20 μm or more and 90 μm or less. If the thickness is less than 10 μm, the solar reflectivity may deteriorate. If the thickness is greater than 100 μm, the positioning accuracy of the optical device may be adversely affected, or the film may be separated or broken in a harsh environment.
[0409] Film forming method according to the embodiment
[0410] The film according to this embodiment can be formed by any coating method and any curing method as long as the coating material according to this embodiment can be uniformly coated to have a thickness of 10 μm or more and 100 μm or less.
[0411] Examples of the coating method of the heat shielding film for optical devices according to this embodiment include brush coating, spray coating, dip coating and transfer. The heat shielding film may be composed of a single coating or multiple coatings, or may be granulated to achieve a good design.
[0412] The curing method of the film for the article or optical device according to this embodiment may be a method of leaving the coating at room temperature, a method of promoting curing by any heating process, or a method of applying ultraviolet rays. In the method of curing by a heating process, for example, a heating furnace, a heater or infrared heating may be used. The curing temperature is preferably room temperature to 400°C, and more preferably room temperature to 200°C.
[0413] Membrane properties
[0414] Solar reflectance
[0415] The solar reflectance of the film according to this embodiment can be set to 60% or more. If the solar reflectance is less than 60%, the temperature reduction effect is deteriorated.
[0416] brightness
[0417] The brightness L of the film according to this embodiment is * It is preferably 60 or more and 90 or less, and more preferably 71 or more and 80 or less. If the brightness is less than 60, the temperature rise reduction effect is deteriorated. If the brightness is 90 or more, the film becomes white, which may deteriorate the antifouling performance.
[0418] Example
[0419] Hereinafter, suitable examples in this embodiment will be described.
[0420] Preparation of coating materials, formation of films, and evaluation of film properties in Examples 28 to 37 were performed by the following methods.
[0421] Observation of membrane cross section
[0422] Use optical microscope to observe the cross section of film.Then, use image analysis software (Image-Pro Plus manufactured by Media Cybernetics) to process cross section image, to evaluate the content distribution of organic pigment in thickness direction.This cross section is divided into 10 parts in the thickness direction from substrate interface to air interface, to evaluate the content distribution of organic pigment in thickness direction.
[0423] Evaluation of design
[0424] The brightness L was measured by using a colorimeter (SE-7700, NIPPON DENSHOKU INDUSTRIES Co., Ltd.) * To evaluate the design. A coating film was formed on a SUS foil to prepare a sample for measurement. First, the coating according to an embodiment of the present invention was applied to the SUS foil to have a thickness of 50 μm and then cured in a firing furnace. After the coating film was formed, the L of the film on the air interface side was measured using a colorimeter. * Subsequently, the film was peeled off from the SUS foil, and then the L * The presence or absence distribution of the organic pigment on the air interface side in the thickness direction was evaluated by comparing the brightness of the coating film on the air interface side and the brightness of the coating film on the substrate (SUS foil) interface side.
[0425] The case where the brightness difference (ΔL*) was 0.2 or more and the brightness on the air interface side was lower than that on the substrate interface side was evaluated as a film A in which a large amount of organic pigment was distributed on the air interface side. The case where the brightness difference (ΔL*) was 0.2 or more and the brightness on the air interface side was higher than that on the substrate interface side was evaluated as a film B in which a small amount of organic pigment was distributed on the air interface side. The case where the brightness difference (ΔL*) was less than 0.2 was evaluated as a film C in which the organic pigment was uniformly distributed in the coating film.
[0426] A: Brightness difference is 0.2 or more and brightness on the air interface side < brightness on the substrate interface side
[0427] B: Brightness difference is 0.2 or more and brightness on the air interface side > brightness on the substrate interface side
[0428] C: Brightness difference is less than 0.2
[0429] In the present invention, the film A has a good design because even if the amount of the organic pigment for adjusting brightness is small compared with the films B and C, the color tone of the film A can be adjusted to a desired color tone.
[0430] Evaluation of thermal insulation performance
[0431] Evaluation of thermal insulation performance based on solar reflectance The solar reflectance was measured and calculated by using the same instrument and method as in the first embodiment.
[0432] A coating film was formed on a SUS foil to prepare a sample for measurement. Specifically, the coating material according to an embodiment of the present invention was applied to a SUS foil to have a thickness of 50 μm, and cured in a firing furnace to form a coating film.
[0433] When the solar reflectance is 70% or more, the film is an excellent film because the cooling effect is high. When the solar reflectance is 60% or more and less than 70%, the film is a good film because the cooling effect is relatively high. When the solar reflectance is less than 60%, the film is a poor film because the cooling effect is reduced.
[0434] A: Solar reflectance is 70% or more.
[0435] B: The solar reflectance is 60% or more and less than 70%.
[0436] C: Solar reflectivity is less than 60%
[0437] In the present invention, when the evaluation result of the solar reflectance is A or B, good heat insulation performance is achieved.
[0438] Durability Evaluation
[0439] The durability of the coating film was evaluated by the following method. A film according to an embodiment of the present invention was formed on a metal plate having a size of 80 mm × 160 mm and a thickness of 1 mm to prepare a sample for measurement. The metal plate was formed of stainless steel, aluminum, titanium or a magnesium alloy. First, a coating according to an embodiment of the present invention was applied to a metal plate to have a thickness of 50 μm and cured in a firing furnace to form a coating film. Subsequently, the sample was repeatedly subjected to 100 thermal shocks in the range of -30°C to 80°C, and then the appearance of the coating film was evaluated.
[0440] When the appearance is substantially unchanged (A), the film is a film with very high durability. When the appearance, etc. is slightly changed (B), the film is a film with relatively high durability. When the film is broken or separated (C), the film is a film with low durability.
[0441] A: Very durable membrane
[0442] B: Film with relatively high durability
[0443] C: Film with low durability
[0444] In the present invention, when the evaluation result of durability is A or B, the film has no problem in durability.
[0445] Embodiment 28
[0446] Coating preparation
[0447] In embodiment 28, coating is prepared by the following method. That is, weigh 100g resin (45.9 volume % in coating film), 130g inorganic pigment (titanium dioxide coated with silicon dioxide) (29.3 volume % in coating film) and 1.0g organic pigment (0.5 volume % in coating film). In addition, weigh 4.0g colored inorganic pigment (0.7 volume % in coating film), 5.0g dispersant (4.1 volume % in coating film) and 100g solvent. Use ball mill to stir them for 15 hours to obtain host. 1 gram of curing agent (18.4 volume %) is mixed with 10g obtained host to prepare the coating in embodiment 28.
[0448] The resin used was Olester Q-691 (Mitsui Chemicals, Inc.). The organic pigment used was CHROMOFINE BLACK A1103 (Dainichiseika Color & Chemicals Mfg. Co., Ltd.). The colored inorganic pigment used was #5950 (Asahi sangyo Kaisha, Ltd.). The dispersant used was DISPERBYK-180 (BYK Japan KK). The inorganic pigment (silica-coated titanium dioxide) used was D-970 (SAKAI CHEMICAL INDUSTRY Co., Ltd., average particle size 0.26 μm). The curing agent used was Takenate D-120N (Mitsui Chemicals, Inc.).
[0449] Film formation
[0450] In Example 28, a film was formed by the following method. The above coating material was applied to a metal plate formed of a magnesium alloy using a spin coater to have a thickness of 50 μm, dried at room temperature overnight, and then fired at 130° C. for 30 minutes to form the film in Example 28. In addition, the coating material was applied to each of a SUS foil and a metal plate using a bar coater to have a thickness of 50 μm, dried at room temperature overnight, and then fired at 130° C. for 30 minutes to obtain the film in Example 28.
[0451] Examples 29 to 37
[0452] In Examples 29 to 37, coatings and films were prepared in the same manner as in Example 28, except that the materials and conditions listed in Tables 9 and 10 were used. The inorganic pigment (titanium dioxide coated with silica) used in Example 29 was QSC-100 (Denka Company Limited, average particle size 0.11 μm). The inorganic pigment (titanium dioxide coated with silica) used in Embodiment 30 was R-38L (SAKAI CHEMICAL INDUSTRY Co., Ltd., average particle size 0.4 μm). The organic pigment used in Example 31 was CI Pigment Black 32 (BASF, average particle size 0.2 μm) used as a perylene pigment. The dispersant used in Example 33 was DISPERBYK (BYK Japan KK). The dispersant used in Example 34 was ANTI-TERRA-250 (BYK Japan KK). The dispersant used in Example 35 was DISPERBYK-187 (BYK Japan KK).
[0453] Comparative Examples 13 to 19
[0454] In Comparative Examples 13 to 19, films were formed in the same manner as in Example 28, except that the materials and conditions listed in Table 9 were used. The inorganic pigment (titanium dioxide coated with silica) used in Comparative Example 13 was HT0210 (TOHO TITANIUM Co., Ltd., average particle size 2.25 μm). The inorganic pigment (titanium dioxide coated with silica) used in Comparative Example 14 was MT-700B (TAYCA Corporation, average particle size 0.08 μm). The dispersant used in Comparative Example 17 was DISPERBYK-145 (BYK Japan KK). The dispersant used in Comparative Example 18 was ANTI-TERRA-108 (BYK Japan KK). The dispersant used in Comparative Example 19 was DISPERBYK-2008 (BYK Japan KK). Table 11 shows the materials used for the films in Comparative Examples 13-16 and the contents of the materials. Table 12 shows the evaluation results of the films in Comparative Examples 17 to 19.
[0455] Table 9
[0456]
[0457] Table 10
[0458]
[0459] Table 11
[0460]
[0461] Table 12
[0462]
[0463] Evaluation results
[0464] Table 13 shows the results of design, thermal insulation performance, and durability evaluated by the above-mentioned methods for the films in Examples 28 to 37 and Comparative Examples 13 to 19.
[0465] When an evaluation result of "C" is given, the film is judged to be an unnecessary film formed on the surface of the optical device.
[0466] Table 13
[0467]
[0468]
[0469] The film formed on the upper surface of the optical device according to the embodiment of the present invention can be used for optical devices such as lens barrels of cameras, camcorders, and broadcasting equipment, as well as camera bodies, camcorder bodies, surveillance cameras, and weather cameras that can be used outdoors.
[0470] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.
Claims
1. An article comprising a substrate and a film formed on the outer side of the substrate, the outer side being a side exposed to an external environment, wherein the film comprises: Resin; Azo organic particles; and Particles containing Ti, O and metal elements other than Ti, and wherein the resin is one or a combination of two or more selected from the following: epoxy resin, polyurethane resin, acrylic resin, polyurethane-acrylic resin, phenolic resin and alkyd resin; wherein when the film is irradiated with sunlight, the brightness of the azo-based organic particles increases, and the particles containing Ti, O and metal elements other than Ti reduce the brightness of the resin due to the photocatalytic effect of the particles containing Ti, O and metal elements other than Ti, Wherein, when the content of the azo organic particles is 100 area %, the content of the particles containing Ti, O and metal elements other than Ti is greater than 25 area % and less than 1000 area %; When the film has a cross-sectional area of 100 area%, the content of the azo organic particles is greater than 0.1 area% and less than 0.4 area% and the content of the particles containing Ti, O and metal elements other than Ti is greater than 0.1 area% and less than 1.0 area%.
2. The article according to claim 1, having a brightness of 50 or more.
3. The article according to claim 1, wherein the metal element other than Ti is Sb, Cr, Fe or Zn. The article according to claim 1 , wherein the azo-based organic particles are particles of azomethine black.
5. The article of claim 1, wherein the film further comprises titanium oxide particles, the surfaces of the titanium oxide particles being coated with silicon dioxide.
6. The article of claim 5, wherein the film further comprises silica particles. The article according to claim 6 , wherein the brightness of the film is 71 or more and 80 or less.
8. The article according to claim 3, wherein the particles containing Ti, O and metal elements other than Ti are: Particles of a material selected from (Ti, Sb, Cr)O2 and (Ti, Fe, Zn)O2, or Particles of a mixture of (Ti,Sb,Cr)O2 and (Ti,Fe,Zn)O2.
9. An optical device comprising: membrane, The film contains a resin, azo organic particles and particles containing Ti, O and metal elements other than Ti. wherein the resin is one or a combination of two or more selected from the following: epoxy resin, polyurethane resin, acrylic resin, polyurethane-acrylic resin, phenolic resin and alkyd resin; wherein when the film is irradiated with sunlight, the brightness of the azo-based organic particles increases, and the particles containing Ti, O and metal elements other than Ti reduce the brightness of the resin due to the photocatalytic effect of the particles containing Ti, O and metal elements other than Ti, and wherein the film is formed on an outer surface of the optical device, When the content of the azo organic particles is 100 area %, the content of the particles containing Ti, O and metal elements other than Ti is 25 area % or more and 1000 area % or less, When the film has a cross-sectional area of 100 area%, the content of the azo organic particles is greater than 0.1 area% and less than 0.4 area% and the content of the particles containing Ti, O and metal elements other than Ti is greater than 0.1 area% and less than 1.0 area%.
10. The optical device according to claim 9, having a brightness of 50 or more.
11. The optical device according to claim 9, wherein the metal element other than Ti is Sb, Cr, Fe or Zn. 12 . The optical device according to claim 9 , wherein the azo-based organic particles are particles of azomethine black.
13. The optical device according to claim 9, wherein the film further contains titanium oxide particles, the surfaces of which are coated with silicon dioxide.
14. The optical device of claim 13, wherein the film further comprises silica particles. The optical device according to claim 14 , wherein the brightness of the film is 71 or more and 80 or less.
16. The optical device according to claim 11, wherein the particles containing Ti, O and metal elements other than Ti are: Particles of a material selected from titanium dioxide, (Ti,Sb,Cr)O2 and (Ti,Fe,Zn)O2, or Particles of a mixture of materials selected from titanium dioxide, (Ti,Sb,Cr)O2 and (Ti,Fe,Zn)O2.
17. A coating comprising: Resin, the resin is selected from the following one or a combination of two or more: epoxy resin, polyurethane resin, acrylic resin, polyurethane - acrylic resin, phenolic resin and alkyd resin; Azo organic particles; and Particles containing Ti, O and metal elements other than Ti, wherein when a film formed by the coating material is irradiated with sunlight, the brightness of the azo organic particles increases, and the particles containing Ti, O and metal elements other than Ti reduce the brightness of the resin due to the photocatalytic effect of the particles containing Ti, O and metal elements other than Ti, When the content of the azo organic particles is 100 parts by weight, the content of the particles containing Ti, O and metal elements other than Ti is 10 parts by weight or more and 1600 parts by weight or less. The coating also comprises a non-volatile component, in, The content of the azo organic particles is 0.1 wt% or more and 1.0 wt% or less relative to the non-volatile component, and The content of the particles containing Ti, O and a metal element other than Ti is 0.1 wt % or more and 1.6 wt % or less relative to the non-volatile component.
18. The coating material according to claim 17, wherein the metal element other than Ti is Sb, Cr, Fe or Zn.
19. The coating material according to claim 18, wherein the particles containing Ti, O and metal elements other than Ti are: Particles of a material selected from (Ti, Sb, Cr)O2 and (Ti, Fe, Zn)O2, or Particles of a mixture of (Ti,Sb,Cr)O2 and (Ti,Fe,Zn)O2. 20 . The coating material according to claim 19 , wherein the azo organic particles are particles of azomethine black.
21. The coating material according to claim 20, further comprising titanium oxide particles, surfaces of which are coated with silicon dioxide.
22. The coating of claim 21 further comprising silica particles.
Citation Information
Patent Citations
Lens barrel and imaging system
JP2009139856A
Heat shield cylinder
JP2011085235A
Titanium dioxide
CN102762670A